Laminate, touch panel member, and display device

By placing an intermediate layer containing the resin base component between the optical resin layer and the resin base material, the problem of reducing adhesion caused by ultraviolet ray deterioration of the resin base material is solved, and the hardness and bending resistance are maintained.

CN119894671APending Publication Date: 2025-04-25DAI NIPPON PRINTING CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202380066926.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-20
Filing Date
2023-09-19
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The resin substrate deteriorates under ultraviolet exposure, resulting in a decrease in adhesion to the optical resin layer, affecting hardness and bending resistance.

Method used

An intermediate layer containing the first component constituting the resin substrate is arranged between the optical resin layer and the resin substrate, and the content of the first component of each layer is adjusted by the AFM-IR method to ensure adhesion between the resin substrate and the optical resin layer.

Benefits of technology

The ultraviolet ray deterioration of the resin substrate is effectively suppressed, and the adhesion between the resin substrate and the optical resin layer is maintained, thereby avoiding the reduction of hardness characteristics and bending resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894671A_ABST
    Figure CN119894671A_ABST
Patent Text Reader

Abstract

The present disclosure provides a laminate having an optical resin layer, a first intermediate layer, a second intermediate layer, and a resin base material in this order, the first intermediate layer and the second intermediate layer each containing a first component constituting the resin base material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a laminate, and a touch panel member and a display device using the laminate. Background Art

[0002] A laminate having an optical resin layer having various properties such as hard coating, scratch resistance, antireflection, antiglare, antistatic, and antifouling properties is disposed on the surface of a display device, a touch panel, or the like.

[0003] Recently, flexible displays such as foldable displays, rollable displays, and bendable displays have attracted attention, and development of laminates to be arranged on the surface of flexible displays has been underway.

[0004] The laminated body comprises a substrate and an optical resin layer disposed on one surface of the substrate. In recent years, from the viewpoints of processability, light weight, thinness, flexibility, etc., the substrate is being replaced from a glass substrate to a resin substrate.

[0005] On the other hand, there is a problem that the resin substrate is degraded by ultraviolet rays. Due to ultraviolet degradation of the resin substrate, the adhesion between the resin substrate and the optical resin layer is reduced.

[0006] As a technique for inhibiting ultraviolet degradation of a resin substrate, a method of using an ultraviolet absorber is known. For example, Patent Document 1 discloses that in order to improve weather resistance, in a laminate having a polyimide film and a hard coat layer, an ultraviolet absorber is contained in the hard coat layer. In addition, for example, Patent Document 2 discloses that in order to improve ultraviolet durability, an ultraviolet absorber is contained in the polyimide film. In addition, for example, Patent Document 3 discloses that in order to improve weather resistance, in a laminate having a polyimide film and a functional layer, an ultraviolet absorber is biased to the surface side of the functional layer side of the polyimide film.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2020-203479

[0010] Patent Document 2: Japanese Patent No. 6358358

[0011] Patent Document 3: Japanese Patent Application Publication No. 2019-73013 Summary of the invention

[0012] Problems to be solved by the invention

[0013] However, when a UV absorber is contained in the hard coat layer, there is a possibility that the UV absorber may inhibit curing and the properties of the hard coat layer, particularly the hardness property, may be impaired.

[0014] In addition, when the ultraviolet absorber is biased on the surface side of the functional layer side of the polyimide film, it is preferred to reduce the thickness of the region containing the ultraviolet absorber in the polyimide film from the perspective of bending resistance. On the other hand, in order to obtain the desired weather resistance, it is necessary to contain a certain amount of ultraviolet absorber, but the thinner the thickness of the region containing the ultraviolet absorber, the more the content of the ultraviolet absorber is relatively, so the bending resistance may be reduced.

[0015] The present disclosure has been made in view of the above-mentioned actual situation, and a main object thereof is to provide a laminate that can suppress a decrease in adhesion between a resin substrate and an optical resin layer due to ultraviolet degradation of the resin substrate even without using an ultraviolet absorber.

[0016] Means for solving problems

[0017] One embodiment of the present disclosure provides a laminate including an optical resin layer, a first intermediate layer, a second intermediate layer, and a resin substrate in this order, wherein the first intermediate layer and the second intermediate layer each contain a first component constituting the resin substrate.

[0018] Another embodiment of the present disclosure provides a laminate including an optical resin layer, an intermediate layer, and a resin substrate in this order, wherein the intermediate layer contains a first component constituting the resin substrate and a second component constituting the optical resin layer.

[0019] Another embodiment of the present invention provides a laminate, which has an optical resin layer, an intermediate layer and a resin substrate in sequence, the intermediate layer contains a first component constituting the resin substrate, and after the laminate is subjected to an accelerated weathering test based on the following JIS K5600-7-8:1999, and then an adhesion test is performed by a checkerboard tape method based on JIS K5400-8.5.2, the number of grids remaining in 100 grids is greater than 90.

[0020] (Conditions that promote weathering test)

[0021] Procedure: Method A involves exposure to water vapor condensation

[0022] UV light: Type 2 UVA (340)

[0023] Irradiation: irradiance 0.63W / m 2 , temperature 23±5℃, black panel temperature 60±3℃, irradiation time 4 hours

[0024] Water vapor condensation: Black panel temperature 50±3℃, water condensation time 4 hours

[0025] 1 cycle: The above irradiation and the above water vapor condensation are performed in sequence as 1 cycle

[0026] Number of cycles: 12 cycles

[0027] Another embodiment of the present disclosure provides a touch panel member including the above-mentioned laminated body on a surface.

[0028] Another embodiment of the present disclosure provides a display device including a display panel and the stacked body disposed on a viewer side of the display panel.

[0029] Effects of the Invention

[0030] In the present disclosure, even without using an ultraviolet absorber, it is possible to suppress a decrease in the adhesion between the resin substrate and the optical resin layer due to ultraviolet degradation of the resin substrate. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 is a schematic cross-sectional view illustrating a laminated body in the present disclosure.

[0032] Figure 2 is a schematic cross-sectional view illustrating a laminated body in the present disclosure.

[0033] Figure 3 is a schematic diagram illustrating a dynamic bending test.

[0034] Figure 4 is a schematic cross-sectional view illustrating a laminated body in the present disclosure.

[0035] Figure 5 is a schematic cross-sectional view illustrating a display device in the present disclosure. DETAILED DESCRIPTION

[0036] Hereinafter, the embodiments of the present invention will be described with reference to the accompanying drawings, etc. Among them, the present invention can be implemented in a variety of different ways, and is not to be construed as being limited to the contents of the embodiments illustrated below. In addition, in order to make the description clearer, the drawings sometimes schematically represent the width, thickness, shape, etc. of each part compared to the actual situation, but it is always an example and does not limit the interpretation of the present invention. In addition, in this specification and the drawings, the same reference numerals are given to the same elements as those in the drawings that have appeared, and the detailed description is sometimes appropriately omitted.

[0037] In this specification, when describing a method of arranging another component above a certain component, if it is simply described as "above" or "below", unless otherwise stated, it includes both the case where the other component is arranged directly above or directly below in a manner of contacting the certain component, and the case where the other component is arranged above or below the certain component with another component further interposed therebetween. In addition, in this specification, when describing a method of arranging another component on the surface of a certain component, if it is simply described as "surface", unless otherwise stated, it includes both the case where the other component is arranged directly above or directly below in a manner of contacting the certain component, and the case where the other component is arranged above or below the certain component with another component further interposed therebetween.

[0038] Hereinafter, the laminated body, the touch panel member, and the display device in the present disclosure will be described in detail.

[0039] A. Laminated body

[0040] The laminated body in the present disclosure has three embodiments. Hereinafter, each embodiment will be described separately.

[0041] I. First Embodiment

[0042] A first embodiment of the laminate in the present disclosure includes an optical resin layer, a first intermediate layer, a second intermediate layer, and a resin substrate in this order, and the first intermediate layer and the second intermediate layer each contain a first component constituting the resin substrate.

[0043] Figure 1 : is a schematic cross-sectional view showing an example of a laminated body according to this embodiment. Figure 1 As shown, the laminate 1A includes an optical resin layer 2, a first intermediate layer 3, a second intermediate layer 4, and a resin base material 5 in this order. The first intermediate layer 3 and the second intermediate layer 4 each contain a first component constituting the resin base material 5.

[0044] In this embodiment, the first intermediate layer and the second intermediate layer containing the first component constituting the resin substrate are disposed between the optical resin layer and the resin substrate, thereby improving the adhesion between the optical resin layer and the resin substrate.

[0045] Here, in the laminate, when ultraviolet rays are irradiated from the surface of the optical resin layer side of the laminate, in the resin substrate, degradation is carried out from the surface of the optical resin layer side of the resin substrate. In the present embodiment, the first intermediate layer and the second intermediate layer disposed between the optical resin layer and the resin substrate contain the first component constituting the resin substrate, so even if the first component contained in the first intermediate layer and the second intermediate layer deteriorates due to ultraviolet rays, the degradation of the resin substrate due to ultraviolet rays can be suppressed. That is, the first intermediate layer and the second intermediate layer can absorb ultraviolet rays, so the ultraviolet degradation of the resin substrate can be suppressed. Thus, the ultraviolet degradation of the resin substrate can be suppressed, and the adhesion of the optical resin layer and the resin substrate can be maintained.

[0046] Thus, in the present embodiment, even if the ultraviolet light absorber is not used, the decrease in the adhesion between the optical resin layer and the resin substrate caused by the ultraviolet light degradation of the resin substrate can be suppressed. Therefore, the hardness characteristics of the optical resin layer can be suppressed to be reduced as in the past because the optical resin layer contains the ultraviolet light absorber. In addition, the bending resistance can be suppressed to be reduced as in the past because the ultraviolet light absorber is biased to the surface side of the optical resin layer side of the resin substrate.

[0047] Hereinafter, each structure of the laminated body of this embodiment will be described.

[0048] 1. Resin substrate

[0049] The resin substrate in the present embodiment is a member that supports an optical resin layer described later.

[0050] (1) Materials of resin substrate

[0051] The resin constituting the resin substrate is not particularly limited as long as it is a resin that can obtain a transparent resin substrate. Among them, the resin substrate preferably contains a resin having at least one selected from the group consisting of an imide skeleton, an amide skeleton and an ester skeleton. These resins are prone to ultraviolet degradation. Therefore, by applying the present disclosure, the reduction in adhesion caused by ultraviolet degradation can be suppressed. In particular, the resin substrate preferably contains a resin having at least an imide skeleton. The resin having an imide skeleton easily absorbs ultraviolet rays and is therefore prone to ultraviolet degradation. Therefore, by applying the present disclosure, the reduction in adhesion caused by ultraviolet degradation can be effectively suppressed.

[0052] Examples of the above-mentioned resins include polyimide resins, polyamide resins, polyester resins, acrylic resins, and triacetyl cellulose. Examples of the polyimide resins include polyimide, polyamideimide, polyetherimide, and polyesterimide. Examples of the polyester resins include polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate. Among them, polyimide resins and polyethylene naphthalate are preferred. In particular, from the viewpoint of flexibility and bending resistance, polyimide, polyamideimide, and polyethylene naphthalate are preferred.

[0053] Hereinafter, polyimide and polyamide-imide will be described as examples.

[0054] (a) Polyimide

[0055] Polyimide is obtained by reacting a tetracarboxylic acid component with a diamine component. The polyimide is not particularly limited as long as it has transparency and rigidity. For example, from the aspect of having excellent transparency and excellent rigidity, it is preferred to have at least one structure selected from the group consisting of the structures represented by the following general formula (1) and the following general formula (3).

[0056] [Chemistry 1]

[0057]

[0058] In the above general formula (1), R 1 represents a tetravalent group which is a tetracarboxylic acid residue, R 2 represents at least one divalent group selected from the group consisting of a trans-cyclohexanediamine residue, a trans-1,4-bismethylenecyclohexanediamine residue, a 4,4'-diaminodiphenyl sulfone residue, a 3,4'-diaminodiphenyl sulfone residue, and a divalent group represented by the following general formula (2). n represents the number of repeating units and is 1 or more.

[0059] [Chemistry 2]

[0060]

[0061] In the above general formula (2), R 3 and R 4 Each independently represents a hydrogen atom, an alkyl group or a perfluoroalkyl group.

[0062] [Chemistry 3]

[0063]

[0064] In the above general formula (3), R 5represents at least one tetravalent group selected from the group consisting of a cyclohexanetetracarboxylic acid residue, a cyclopentanetetracarboxylic acid residue, a dicyclohexane-3,4,3',4'-tetracarboxylic acid residue and a 4,4'-(hexafluoroisopropylidene)diphthalic acid residue, and R 6 represents a divalent group which is a diamine residue. n' represents the number of repeating units and is 1 or more.

[0065] It should be noted that the "tetracarboxylic acid residue" refers to a residue obtained by removing four carboxyl groups from tetracarboxylic acid, and has the same structure as a residue obtained by removing the dianhydride structure from tetracarboxylic dianhydride. In addition, the "diamine residue" refers to a residue obtained by removing two amino groups from diamine.

[0066] In the above general formula (1), R 1 It is a tetracarboxylic acid residue, and may be a residue obtained by removing the dianhydride structure from tetracarboxylic dianhydride. As tetracarboxylic dianhydride, for example, tetracarboxylic dianhydride described in International Publication No. 2018 / 070523 may be mentioned. As R in the above general formula (1), 1 , wherein, from the perspective of improving transparency and improving rigidity, it is preferred to contain at least one selected from the group consisting of 4,4'-(hexafluoroisopropylidene)diphthalic acid residues, 3,3',4,4'-biphenyltetracarboxylic acid residues, pyromellitic acid residues, 2,3',3,4'-biphenyltetracarboxylic acid residues, 3,3',4,4'-benzophenonetetracarboxylic acid residues, 3,3',4,4'-diphenylsulfonetetracarboxylic acid residues, 4,4'-oxydiphthalic acid residues, cyclohexanetetracarboxylic acid residues and cyclopentanetetracarboxylic acid residues, and further preferably contains at least one selected from the group consisting of 4,4'-(hexafluoroisopropylidene)diphthalic acid residues, 4,4'-oxydiphthalic acid residues and 3,3',4,4'-diphenylsulfonetetracarboxylic acid residues.

[0067] R 1 The total amount of these preferred residues is preferably 50 mol% or more, more preferably 70 mol% or more, and even more preferably 90 mol% or more.

[0068] In addition, as R 1 It is also preferred to mix the following group A and group B, wherein group A is a tetracarboxylic acid residue group selected from the group consisting of 3,3',4,4'-biphenyltetracarboxylic acid residues, 3,3',4,4'-benzophenonetetracarboxylic acid residues and pyromellitic acid residues, and at least one such tetracarboxylic acid residue group suitable for improving rigidity, and group B is a tetracarboxylic acid residue group selected from the group consisting of 4,4'-(hexafluoroisopropyl)diphthalic acid residues, 2,3',3,4'-biphenyltetracarboxylic acid residues, 3,3',4,4'-diphenylsulfonetetracarboxylic acid residues, 4,4'-oxydiphthalic acid residues, cyclohexanetetracarboxylic acid residues and cyclopentanetetracarboxylic acid residues, and at least one such tetracarboxylic acid residue group suitable for improving transparency.

[0069] In this case, regarding the content ratio of the tetracarboxylic acid residue group (group A) suitable for improving rigidity and the tetracarboxylic acid residue group (group B) suitable for improving transparency, the tetracarboxylic acid residue group (group A) suitable for improving rigidity is preferably 0.05 mol to 9 mol, more preferably 0.1 mol to 5 mol, and even more preferably 0.3 mol to 4 mol, per 1 mol of the tetracarboxylic acid residue group (group B) suitable for improving transparency.

[0070] As R in the above general formula (1) 2 Among them, from the perspective of improving transparency and improving rigidity, it is preferably at least one divalent group selected from the group consisting of a 4,4'-diaminodiphenyl sulfone residue, a 3,4'-diaminodiphenyl sulfone residue and a divalent group represented by the above general formula (2), and it is further preferably at least one divalent group selected from the group consisting of a 4,4'-diaminodiphenyl sulfone residue, a 3,4'-diaminodiphenyl sulfone residue, and a divalent group represented by the above general formula (2) in which R3 and R4 are perfluoroalkyl groups.

[0071] As R in the above general formula (3) 5 Among them, from the viewpoint of improving transparency and improving rigidity, it is preferred to contain a 4,4′-(hexafluoroisopropylidene)diphthalic acid residue, a 3,3′,4,4′-diphenylsulfonetetracarboxylic acid residue, and an oxydiphthalic acid residue.

[0072] R 5 The preferred residues are preferably contained in an amount of 50 mol% or more, more preferably 70 mol% or more, and even more preferably 90 mol% or more.

[0073] In the above general formula (3), R 6It is a diamine residue, and it can be a residue after removing two amino groups from a diamine. As a diamine, for example, a diamine described in International Publication No. 2018 / 070523 can be cited. As R6 in the above-mentioned general formula (3), from the aspects of improving transparency and improving rigidity, it is preferably selected from 2,2'-bis(trifluoromethyl)benzidine residue, bis[4-(4-aminophenoxy)phenyl]sulfone residue, 4,4'-diaminodiphenylsulfone residue, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane residue, bis[4-(3-aminophenoxy)phenyl]sulfone residue, 4,4'-diamino-2,2'-bis(trifluoromethyl)diphenyl ether residue, 1,4-bis[4-amino-2-(trifluoromethyl)phenoxy]benzene residue, 2,2- It preferably contains at least one divalent group selected from the group consisting of a bis[4-(4-amino-2-trifluoromethylphenoxy)phenyl]hexafluoropropane residue, a 4,4'-diamino-2-(trifluoromethyl)diphenyl ether residue, a 4,4'-diaminobenzanilide residue, an N,N'-bis(4-aminophenyl)terephthalamide residue and a 9,9-bis(4-aminophenyl)fluorene residue, and further preferably contains at least one divalent group selected from the group consisting of a 2,2'-bis(trifluoromethyl)benzidine residue, a bis[4-(4-aminophenoxy)phenyl]sulfone residue and a 4,4'-diaminodiphenylsulfone residue.

[0074] R 6 The total amount of these preferred residues is preferably 50 mol% or more, more preferably 70 mol% or more, and even more preferably 90 mol% or more.

[0075] In addition, as R 6 It is also preferred to use the following group C mixed with group D, wherein group C is a diamine residue group suitable for improving rigidity selected from the group consisting of bis[4-(4-aminophenoxy)phenyl]sulfone residue, 4,4'-diaminobenzanilide residue, N,N'-bis(4-aminophenyl)terephthalamide residue, p-phenylenediamine residue, m-phenylenediamine residue and 4,4'-diaminodiphenylmethane residue, and group D is a diamine residue selected from the group consisting of 2,2'-bis(trifluoromethyl)benzidine residue, 4,4'-diaminodiphenylsulfone residue, 2,2-bis[4-(4-aminophenyl)terephthalamide residue, p-phenylenediamine residue, m-phenylenediamine residue and 4,4'-diaminodiphenylmethane residue. The invention also provides a diamine residue group suitable for improving transparency, which comprises at least one of the group consisting of a bis[4-(3-aminophenoxy)phenyl]hexafluoropropane residue, a bis[4-(3-aminophenoxy)phenyl]sulfone residue, a 4,4'-diamino-2,2'-bis(trifluoromethyl)diphenyl ether residue, a 1,4-bis[4-amino-2-(trifluoromethyl)phenoxy]benzene residue, a 2,2-bis[4-(4-amino-2-trifluoromethylphenoxy)phenyl]hexafluoropropane residue, a 4,4'-diamino-2-(trifluoromethyl)diphenyl ether residue and a 9,9-bis(4-aminophenyl)fluorene residue.

[0076] In this case, regarding the content ratio of the above-mentioned diamine residue group (group C) suitable for improving rigidity and the diamine residue group (group D) suitable for improving transparency, the diamine residue group (group C) suitable for improving rigidity is preferably 0.05 mol to 9 mol, more preferably 0.1 mol to 5 mol, and even more preferably 0.3 mol to 4 mol, relative to 1 mol of the diamine residue group (group D) suitable for improving transparency.

[0077] In the structures represented by the general formula (1) and the general formula (3), n and n' each independently represent the number of repeating units and are greater than 1. The number of repeating units n in the polyimide can be appropriately selected according to the structure and is not particularly limited. The average number of repeating units can be, for example, greater than 10 and less than 2000, preferably greater than 15 and less than 1000.

[0078] The polyimide may contain a polyamide structure in part thereof. Examples of the polyamide structure that may be contained include a polyamideimide structure containing a tricarboxylic acid residue such as trimellitic anhydride, and a polyamide structure containing a dicarboxylic acid residue such as terephthalic acid.

[0079] From the perspective of improving transparency and surface hardness, R 1 or R 5 The tetravalent group of the tetracarboxylic acid residue, and the 2 or R 6 At least one of the divalent groups of the diamine residue preferably contains an aromatic ring and contains at least one selected from the group consisting of (i) fluorine atoms, (ii) aliphatic rings, and (iii) aromatic rings connected to each other with sulfonyl groups or fluorine-substituted or unsubstituted alkylene groups. By making the polyimide contain at least one selected from the tetracarboxylic acid residue with an aromatic ring and the diamine residue with an aromatic ring, the molecular skeleton becomes rigid so that the orientation is improved, the surface hardness is improved, but the rigid aromatic ring skeleton has a tendency to extend the absorption wavelength to a long wavelength, and the transmittance in the visible light region tends to decrease. On the other hand, if the polyimide contains (i) fluorine atoms, the transparency is improved from the aspect that the electronic state in the polyimide skeleton is not easy to transfer charge. In addition, if the polyimide contains (ii) aliphatic rings, the transparency is improved from the aspect that the movement of the charge in the skeleton can be hindered by cutting the conjugation of the π electrons in the polyimide skeleton. When the polyimide includes (iii) a structure in which aromatic rings are linked to each other via a sulfonyl group or a fluorine-substituted or unsubstituted alkylene group, the transparency is improved because the conjugation of π electrons in the polyimide skeleton can be interrupted to inhibit the movement of charges in the skeleton.

[0080] Among them, from the perspective of improving transparency and surface hardness, R 1 or R5 The tetravalent group of the tetracarboxylic acid residue, and the 2 or R 6 At least one of the divalent groups of the diamine residue preferably contains an aromatic ring and a fluorine atom, and as R 2 or R 6 The divalent group of the diamine residue preferably contains an aromatic ring and a fluorine atom.

[0081] As a specific example of such a polyimide, a substance having a specific structure described in International Publication No. 2018 / 070523 can be mentioned.

[0082] The polyimide can be synthesized by a known method. In addition, commercially available polyimides can be used. Examples of commercially available polyimides include Neopulim (registered trademark) manufactured by Mitsubishi Gas Chemical Co., Ltd.

[0083] The weight average molecular weight of the polyimide is, for example, preferably 3000 to 500,000, more preferably 5000 to 300,000, and further preferably 10,000 to 200,000. If the weight average molecular weight is too small, sufficient strength may not be obtained, and if the weight average molecular weight is too large, viscosity increases and solubility decreases, so a polyimide substrate having a smooth surface and uniform thickness may not be obtained.

[0084] It should be noted that the weight average molecular weight of polyimide can be measured by gel permeation chromatography (GPC). Specifically, polyimide is made into a 0.1 mass% concentration of N-methylpyrrolidone (NMP) solution, and the developing solvent uses a 30mmol% LiBr-NMP solution with a water content of less than 500ppm, using a GPC device manufactured by Tosoh (HLC-8120, column used: GPC LF-804 manufactured by SHODEX), and is measured under the conditions of sample injection volume 50μL, solvent flow rate 0.4mL / min, and 37°C. The weight average molecular weight is obtained by using a polystyrene standard sample with the same concentration as the sample as a benchmark.

[0085] (b) Polyamide-imide

[0086] As a polyamide-imide, a substance having the following first block and second block, the first block includes a structural unit derived from a dianhydride and a structural unit derived from a diamine, and the second block includes a structural unit derived from an aromatic dicarbonyl compound and a structural unit derived from an aromatic diamine. In the above-mentioned polyamide-imide, the above-mentioned dianhydride may include, for example, biphenyltetracarboxylic dianhydride (BPDA) and 2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride (6FDA). In addition, the above-mentioned diamine may include bistrifluoromethylbenzidine (TFDB). That is, the above-mentioned polyamide-imide has a structure in which a polyamide-imide precursor having the following first block and second block is imidized, the first block is formed by copolymerizing a monomer containing a dianhydride and a diamine, and the second block is formed by copolymerizing a monomer containing an aromatic dicarbonyl compound and an aromatic diamine. The polyamide-imide has a first block including an imide bond and a second block including an amide bond, so that not only optical properties but also thermal properties and mechanical properties are excellent. In particular, by using bistrifluoromethylbenzidine (TFDB) as a diamine forming the first block, thermal stability and optical properties can be improved. In addition, by using 2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride (6FDA) and biphenyltetracarboxylic dianhydride (BPDA) as dianhydrides forming the first block, birefringence can be improved and heat resistance can be ensured.

[0087] The dianhydride forming the first block includes two dianhydrides, namely 6FDA and BPDA. In the first block, the polymer to which TFDB and 6FDA are bonded and the polymer to which TFDB and BPDA are bonded may be separately contained based on different repeating units, or may be arranged regularly in the same repeating unit, or may be contained in a completely random arrangement.

[0088] The monomers forming the first block preferably contain BPDA and 6FDA as dianhydrides at a molar ratio of 1:3 to 3:1. This is because optical properties can be ensured while reduction in mechanical properties and heat resistance can be suppressed, thereby achieving excellent birefringence.

[0089] The molar ratio of the first block to the second block is preferably 5:1 to 1:1. When the content of the second block is significantly low, the improvement effect of the thermal stability and mechanical properties brought by the second block cannot be fully obtained. In addition, when the content of the second block is further higher than the content of the first block, the thermal stability and mechanical properties can be improved, but sometimes the optical properties such as yellowness and transmittance are reduced, and the birefringence characteristics are also improved. It should be noted that the first block and the second block can be random copolymers or block copolymers. The repeating unit of the block is not particularly limited.

[0090] Examples of the aromatic dicarbonyl compound forming the second block include at least one selected from the group consisting of p-Terephthaloyl chloride (TPC), terephthalic acid (Terephthalic acid), isophthaloyl dichloride (Iso-phthaloyl dichloride) and 4,4'-benzoyl chloride (4,4'-benzoyl chloride). Preferably, it may be at least one selected from p-Terephthaloyl chloride (TPC) and isophthaloyl dichloride (Iso-phthaloyl dichloride).

[0091] Examples of the diamine forming the second block include 2,2-bis(4-(4-aminophenoxy)phenyl)hexafluoropropane (HFBAPP), bis(4-(4-aminophenoxy)phenyl)sulfone (BAPS), bis(4-(3-aminophenoxy)phenyl)sulfone (BAPSM), 4,4'-diaminodiphenylsulfone (4DDS), 3,3'-diaminodiphenylsulfone (3DDS), 2,2-bis(4-(4-aminophenoxy)phenylpropane (BAPP), 4,4'-diaminodiphenylpropane (6HDA), 1,3-bis(4-aminophenoxy)benzene (134A) and 1,3-bis(4-aminophenoxy)phenylsulfone (134B). PB), 1,3-bis(3-aminophenoxy)benzene (133APB), 1,4-bis(4-aminophenoxy)biphenyl (BAPB), 4,4'-bis(4-amino-2-trifluoromethylphenoxy)biphenyl (6FAPBP), 3,3-diamino-4,4-dihydroxydiphenyl sulfone (DABS), 2,2-bis(3-amino-4-hydroxyoxyphenyl)propane (BAP), 4,4'-diaminodiphenylmethane (DDM), 4,4'-oxydiphenylamine (4-ODA) and 3,3'-oxydiphenylamine (3-ODA).

[0092] In the case of using an aromatic dicarbonyl compound, high thermal stability and mechanical properties are easily achieved, but due to the benzene ring in the molecular structure, high birefringence is sometimes shown. Therefore, in order to suppress the reduction of birefringence caused by the second block, diamines preferably use diamines with soft groups introduced into the molecular structure. Specifically, diamines are more preferably selected from bis (4- (3-aminophenoxy) phenyl) sulfone (BAPSM), 4,4'-diaminodiphenyl sulfone (4DDS) and 2,2-bis (4- (4-aminophenoxy) phenyl) hexafluoropropane (HFBAPP) One or more diamines. In particular, the longer the length of the soft group is like BAPSM and the position of the substituent is in the meta position of the diamine, the more excellent birefringence can be shown.

[0093] The polyamide-imide precursor including the following first block and second block in its molecular structure has a weight average molecular weight of, for example, preferably 200,000 to 215,000 as measured by GPC, and a viscosity of, for example, preferably 2400 poise to 2600 poise, wherein the first block is copolymerized with a dianhydride including biphenyltetracarboxylic dianhydride (BPDA) and 2-bis(3,4-dicarboxyphenyl)hexafluoropropane dianhydride (6FDA) and a diamine including bistrifluoromethylbenzidine (TFDB), and the second block is copolymerized with an aromatic dicarbonyl compound and an aromatic diamine.

[0094] Polyamideimide can be obtained by imidizing a polyamideimide precursor. In addition, polyamideimide can be used to obtain a polyamideimide film. Regarding the method of imidizing a polyamideimide precursor and the method for producing a polyamideimide film, for example, reference can be made to Japanese Patent Table No. 2018-506611.

[0095] (2) Composition of resin substrate

[0096] The thickness of the resin substrate is not particularly limited as long as it is a thickness that can have flexibility. The thickness of the resin substrate is, for example, preferably 10 μm or more and 100 μm or less, more preferably 25 μm or more and 80 μm or less. By making the thickness of the resin substrate within the above range, good flexibility can be obtained, and sufficient hardness can be obtained. In addition, the curling of the laminate can also be suppressed. Furthermore, it is preferred in terms of lightweighting of the laminate.

[0097] The indentation hardness of the resin substrate is preferably larger than the indentation hardness of the first intermediate layer and the indentation hardness of the second intermediate layer. The flexural resistance of the laminate becomes good.

[0098] The indentation hardness of the resin substrate is preferably greater than the indentation hardness of the first intermediate layer and the second intermediate layer, for example, 240 MPa to 600 MPa, 280 MPa to 550 MPa, or 300 MPa to 500 MPa.

[0099] The method for measuring the indentation hardness of the resin substrate is the same as the method for measuring the indentation hardness of the first intermediate layer described below.

[0100] Here, in the measurement of indentation hardness, when the indenter is vertically pressed into the center of the cross section of the resin substrate, in order to avoid the influence of the optical resin layer and the influence of the side edge of the resin substrate, the Berkovich indenter is pressed into the portion of the resin substrate at a distance of more than 500 nm from the interface between the resin substrate and the second intermediate layer to the center side of the resin substrate, and at a distance of more than 500 nm from both side ends of the resin substrate to the center side of the resin substrate. It should be noted that, in the case where an arbitrary layer is arranged on the surface of the resin substrate opposite to the optical resin layer, the Berkovich indenter is pressed into the portion of the resin substrate at a distance of more than 500 nm from the interface between the resin substrate and the arbitrary layer to the center side of the resin substrate.

[0101] In the measurement of the indentation hardness of the resin substrate, a measurement sample may be prepared for the laminate, or a measurement sample may be prepared for only the resin substrate.

[0102] 2. Optical resin layer

[0103] The optical resin layer in the present embodiment is a member disposed on the surface of the first intermediate layer on the opposite side to the second intermediate layer.

[0104] (1) Material of optical resin layer

[0105] The optical resin layer in this embodiment may or may not have hard coating properties, for example. Among them, the optical resin layer preferably has hard coating properties. That is, the optical resin layer is preferably a hard coating layer.

[0106] Here, the optical resin layer having hard coating properties is a layer for increasing the surface hardness, and specifically refers to a layer having a hardness of "H" or higher in the surface on the optical resin layer side of the laminate in a pencil hardness test specified in JIS K5600-5-4:1999.

[0107] When the optical resin layer has hard coating properties, the optical resin layer preferably contains a cured product of a resin composition containing a polymerizable compound. The cured product of the resin composition containing a polymerizable compound can be obtained by polymerizing the polymerizable compound using a polymerization initiator as needed by a known method.

[0108] The polymerizable compound has at least one polymerizable functional group in the molecule. As the polymerizable compound, for example, at least one of a radical polymerizable compound and a cation polymerizable compound can be used.

[0109] A free radical polymerizable compound refers to a compound having a free radical polymerizable group. The free radical polymerizable group possessed by the free radical polymerizable compound is not particularly limited as long as it is a functional group capable of undergoing a free radical polymerization reaction. Examples thereof include groups containing carbon-carbon unsaturated double bonds, specifically, vinyl and (meth)acryloyl groups. It should be noted that when the free radical polymerizable compound has two or more free radical polymerizable groups, these free radical polymerizable groups may be the same or different.

[0110] The number of radically polymerizable groups contained in one molecule of the radically polymerizable compound is preferably 2 or more, more preferably 3 or more, from the viewpoint of increasing the surface hardness of the optical resin layer and improving the scratch resistance.

[0111] For free radical polymerizable compounds, compounds with (meth)acryloyl groups are preferred from the aspect of high reactivity. For example, polyfunctional (meth)acrylate monomers and polyfunctional (meth)acrylate oligomers having multiple (meth)acryloyl groups in the molecule and having a molecular weight of hundreds to thousands are preferred. In addition, polyfunctional (meth)acrylate polymers having two or more (meth)acryloyl groups in the side chain of the acrylate polymer are also preferred. As polyfunctional (meth)acrylate monomers and polyfunctional (meth)acrylate oligomers, for example, urethane (meth)acrylate, polyester (meth)acrylate, epoxy (meth)acrylate, melamine (meth)acrylate, polyfluoroalkyl (meth)acrylate, silicone (meth)acrylate can be cited.

[0112] Among them, a multifunctional (meth) acrylate monomer having more than two (meth) acryloyl groups in one molecule is preferred. By making the optical resin layer contain a cured product of a resin composition containing a multifunctional (meth) acrylate monomer, the surface hardness of the optical resin layer can be increased and the scratch resistance can be improved. Furthermore, the adhesion can also be improved. In addition, a multifunctional (meth) acrylate oligomer or a multifunctional (meth) acrylate polymer having more than two (meth) acryloyl groups in one molecule is also preferred. By making the optical resin layer contain a cured product of a resin composition containing a multifunctional (meth) acrylate oligomer or a multifunctional (meth) acrylate polymer, the surface hardness of the optical resin layer can be increased and the scratch resistance can be improved. In addition, the bending resistance and adhesion can also be improved.

[0113] In addition, in this specification, (meth)acryloyl group means an acryloyl group and a methacryloyl group, respectively. In addition, (meth)acrylate means an acrylate and a methacrylate, respectively.

[0114] In particular, a polyfunctional (meth)acrylate monomer having 3 or more and 6 or less (meth)acryloyl groups in one molecule is preferred. The reactivity is high, the surface hardness of the optical resin layer increases, and the scratch resistance is improved.

[0115] Furthermore, in order to adjust the hardness, adjust the viscosity, improve the adhesion, etc., a monofunctional (meth)acrylate monomer may be further used as a radical polymerizable compound.

[0116] Cationic polymerizable compounds refer to compounds having cationic polymerizable groups. The cationic polymerizable groups possessed by the cationic polymerizable compounds are not particularly limited as long as they are functional groups capable of undergoing cationic polymerization. Examples thereof include epoxy groups, oxetane groups, and vinyl ether groups. It should be noted that when the cationic polymerizable compounds have two or more cationic polymerizable groups, these cationic polymerizable groups may be the same or different.

[0117] The number of cationically polymerizable groups contained in one molecule of the cationically polymerizable compound is preferably 2 or more, more preferably 3 or more, from the viewpoint of increasing the surface hardness of the optical resin layer and improving the scratch resistance.

[0118] Among them, the cationically polymerizable compound is preferably a compound having at least one of an epoxy group and an oxetanyl group as a cationically polymerizable group, and more preferably a compound having two or more of at least one of an epoxy group and an oxetanyl group in one molecule.

[0119] When the optical resin layer does not have hard coating properties, the optical resin layer may be made of, for example, thermoplastic resins, cured resins, etc. The cured resin refers to a resin cured by heat or by irradiation with ionizing radiation such as ultraviolet rays or electron beams.

[0120] The optical resin layer may contain a polymerization initiator as required. As the polymerization initiator, free radical polymerization initiator, cationic polymerization initiator, free radical and cationic polymerization initiator, etc. may be appropriately selected and used. It should be noted that in the optical resin layer, sometimes the polymerization initiator is completely decomposed and no residue remains.

[0121] In addition, the optical resin layer may contain an ultraviolet absorber. The content of the ultraviolet absorber in the optical resin layer is, for example, preferably less than 10 parts by mass, more preferably less than 5 parts by mass, and further preferably less than 1 part by mass relative to 100 parts by mass of the resin component. When the content of the ultraviolet absorber in the optical resin layer is too much, poor curing of the optical resin layer may occur. As a result, the surface hardness of the optical resin layer may decrease.

[0122] Among them, the optical resin layer preferably does not substantially contain an ultraviolet absorber. It is possible to suppress the poor curing of the optical resin layer caused by the ultraviolet absorber. It should be noted that the optical resin layer does not substantially contain an ultraviolet absorber means that the content of the ultraviolet absorber in the optical resin layer is less than 0.5 mass parts relative to 100 mass parts of the resin component. It is particularly preferred that the content of the above-mentioned ultraviolet absorber is 0 mass parts and the optical resin layer does not contain an ultraviolet absorber.

[0123] In addition, the optical resin layer may contain additives as required. As additives, for example, inorganic particles, organic particles, antioxidants, light stabilizers, infrared absorbers, antistatic agents, antifouling agents, antiglare agents, leveling agents, surfactants, lubricants, various sensitizers, flame retardants, tackifiers, polymerization inhibitors and surface modifiers can be cited.

[0124] It should be noted that the components contained in the optical resin layer are analyzed using, for example, Fourier transform infrared spectrophotometer (FTIR), thermal decomposition gas chromatography device (GC-MS), high performance liquid chromatography, gas chromatography mass spectrometer, NMR, elemental analysis, XPS / ESCA, TOF-SIMS and their combination.

[0125] In addition, the optical resin layer may contain the first component constituting the resin substrate. When the resin substrate is composed of a plurality of components, the first intermediate layer may contain at least one component of the components constituting the resin substrate. It should be noted that the first component will be described later.

[0126] When the content of the first component in the resin substrate is set to 100%, the ratio of the content of the first component in the optical resin layer to the content of the first component in the resin substrate is preferably 0% or more and 10% or less. If the above ratio is within the above range, the reduction in the properties of the optical resin layer caused by the first component, especially the reduction in hardness properties, can be suppressed.

[0127] Here, the ratio of the content of the first component in the optical resin layer to the content of the first component in the resin substrate is determined by measuring the cross section of the laminate using the AFM-IR method (AFM-based Infrared Spectroscopy). When the intensity of the peak derived from the first component in the IR spectrum of the resin substrate is used as a reference, the ratio of the intensity of the peak derived from the first component in the IR spectrum of the optical resin layer to the intensity of the peak derived from the first component in the IR spectrum of the resin substrate can be regarded as the ratio of the content of the first component in the optical resin layer to the content of the first component in the resin substrate.

[0128] In the case of the AFM-IR method, first, characteristic peaks of the resin substrate and the optical resin layer are confirmed from the IR spectra of the resin substrate and the optical resin layer.

[0129] For example, when the optical resin layer contains a cured product of a resin composition containing a polymerizable compound having a (meth)acryloyl group, the peak derived from the C═O stretching vibration of the ester group appears at 1725±20 cm -1 The peak of CO stretching vibration originating from the ester group appears at 1145±20cm -1 .

[0130] In addition, the characteristic peaks derived from the resin substrate vary depending on the constituent components of the resin substrate. For example, when the resin substrate contains a polyester resin, the peak derived from the C=O stretching vibration of the ester group appears at 1715±20 cm -1 The peak of CO stretching vibration originating from the aromatic ester group appears at 1240±20cm -1 The peak of CO stretching vibration originating from the ester group appears at 1095±20cm -1 In addition, for example, when the resin substrate contains a polyamide-based resin, the peak derived from the C=O stretching vibration of the amide group appears at 1635±20 cm -1 The peak originating from the -CNH angular vibration of the amide group appears at 1540±20cm -1 The peak of CN stretching vibration originating from the amide group appears at 1265±20cm -1 In addition, for example, when the resin substrate contains a polyimide-based resin, the peak derived from the C═O stretching vibration of the imide group appears at 1725±20 cm -1 The peak originating from the CN stretching vibration of the imide group appears at 1366±20cm -1 .

[0131] Thus, the characteristic peaks are different in the resin substrate and the optical resin layer. Therefore, the ratio of the intensity of the peak in the IR spectrum of the optical resin layer is obtained based on the intensity of the peak from the resin substrate, and thus the ratio of the content of the first component in the optical resin layer relative to the content of the first component in the resin substrate can be obtained.

[0132] As described above, for example, when the resin substrate contains a polyester-based resin, a peak (1715±20 cm -1 ), the peak derived from the CO stretching vibration of the aromatic ester group (1240±20cm -1 ) and the peak derived from the CO stretching vibration of the ester group (1095±20cm -1 Among them, the peak derived from the C=O stretching vibration of the ester group (1715±20cm -1 ) is easy to analyze. Therefore, it is preferred to determine the peak derived from the C=O stretching vibration of the ester group (1715±20 cm -1It should be noted that the peak derived from the C=O stretching vibration of the ester group (1715±20 cm -1 ) is difficult to identify, the peak derived from the CO stretching vibration of the aromatic ester group (1240±20cm -1 ) intensity ratio. In addition, the peak derived from the CO stretching vibration of the aromatic ester group (1240 ± 20 cm -1 ) is difficult to identify, the peak derived from the CO stretching vibration of the ester group (1095±20cm -1 )’s intensity ratio.

[0133] In addition, as described above, for example, when the resin substrate contains a polyamide-based resin, a peak (1635±20 cm -1 ), the peak derived from the -CNH angle vibration of the amide group (1540±20cm -1 ), and the peak derived from the CN stretching vibration of the amide group (1265±20cm -1 Among them, the peak derived from the C=O stretching vibration of the amide group (1635±20cm -1 Therefore, it is preferred to determine the peak (1635±20 cm -1 It should be noted that the peak (1635±20 cm) derived from the C=O stretching vibration of the amide group is difficult to identify. -1 ), the peak derived from the -CNH angular vibration of the amide group (1540±20cm -1 In addition, the peak (1540±20cm -1 ) is difficult to identify, the peak derived from the CN stretching vibration of the amide group (1265±20cm -1 )’s strength ratio.

[0134] In addition, as described above, for example, when the resin substrate contains a polyimide-based resin, a peak (1725±20 cm -1 ) and the peak derived from the CN stretching vibration of the imide group (1366±20cm -1 Among them, the peak derived from the C=O stretching vibration of the imide group (1725±20cm -1 ) is easy to analyze. Therefore, it is preferable to find the peak (1725±20cm -1 It should be noted that the peak derived from the C=O stretching vibration of the imide group (1725±20 cm-1 ) is difficult to identify, the peak derived from the CN stretching vibration of the imide group (1366±20cm -1 )’s strength ratio.

[0135] AFM-IR measurement was performed using nanoIR manufactured by Anasys Instruments Inc. Specific examples of measurement conditions are shown below.

[0136] Light source: tunable pulse laser (1kHz)

[0137] AFM mode: Contact mode (when obtaining AFM-IR spectrum)

[0138] ·Measurement wave number range: 1950cm -1 ~950cm -1

[0139] Wave number resolution: 1.5cm -1

[0140] Coaverages: 512

[0141] Cumulative number of times: 3 times or more

[0142] Polarization angle: 45 degrees

[0143] (2) Composition of optical resin layer

[0144] The optical resin layer may be a single layer or a multi-layer layer.

[0145] In addition, when the optical resin layer has hard coating properties and the optical resin layer is multilayered, the optical resin layer may have a first hard coating layer and a second hard coating layer in order from the first intermediate layer side. In this case, in order to improve the surface hardness and improve the bending resistance, the optical resin layer may have a first hard coating layer for imparting hardness and a second hard coating layer for imparting bending resistance and scratch resistance in order from the first intermediate layer side.

[0146] The thickness of the optical resin layer can be appropriately selected according to the function of the optical resin layer and the purpose of the laminate. The thickness of the optical resin layer is preferably 1 μm or more and 20 μm or less, more preferably 1 μm or more and 15 μm or less, and further preferably 2 μm or more and 5 μm or less. If the thickness of the optical resin layer is too thin, the desired function may not be obtained. In addition, if the thickness of the optical resin layer is too thick, flexibility and bending resistance may be reduced.

[0147] Here, the thickness of the optical resin layer is measured by dyeing the first intermediate layer and the second intermediate layer with a dye in a cross section in the thickness direction of the laminate so that the interface between the first intermediate layer and the optical resin layer can be observed. Specifically, the thickness of the optical resin layer is the average value of the thickness of any 10 points measured from a cross section in the thickness direction of the laminate observed using a scanning transmission electron microscope (STEM). It should be noted that, unless otherwise specified, the method for measuring the thickness of other layers of the laminate is the same.

[0148] The indentation hardness of the optical resin layer is preferably greater than the indentation hardness of the resin substrate. This improves the hardness characteristics of the laminate.

[0149] The indentation hardness of the optical resin layer is preferably greater than the indentation hardness of the first intermediate layer and the indentation hardness of the second intermediate layer. The hardness characteristics and bending resistance of the laminated body are improved.

[0150] The indentation hardness of the optical resin layer is preferably greater than the indentation hardness of the first intermediate layer and the indentation hardness of the second intermediate layer, for example, preferably 400 MPa or more, more preferably 400 MPa or more and 1500 MPa or less, and further preferably 400 MPa or more and 800 MPa or less. By making the indentation hardness of the optical resin layer within the above range, the surface hardness can be increased.

[0151] The method for measuring the indentation hardness of the optical resin layer is the same as the method for measuring the indentation hardness of the first intermediate layer described below.

[0152] Here, in the measurement of indentation hardness, when the indenter is pressed vertically into the center of the cross-section of the optical resin layer, in order to avoid the influence of the resin substrate and to avoid the influence of the side edge of the optical resin layer, the Berkovich indenter is pressed into a portion of the optical resin layer that is more than 500 nm away from the interface between the optical resin layer and the first intermediate layer to the center side of the resin substrate and more than 500 nm away from both side ends of the optical resin layer to the center side of the optical resin layer.

[0153] In the measurement of the indentation hardness of the optical resin layer, a measurement sample may be prepared for the laminate, or a measurement sample may be prepared for only the optical resin layer.

[0154] As a method for forming the optical resin layer, for example, there is a method of applying a resin composition for an optical resin layer and curing it.

[0155] 3. The first intermediate layer

[0156] The first intermediate layer in the present embodiment is disposed between the optical resin layer and the second intermediate layer, and contains the first component constituting the above-mentioned resin base material.

[0157] The first intermediate layer contains the first component constituting the resin substrate. When the resin substrate is composed of a plurality of components, the first intermediate layer only needs to contain at least one component among the components constituting the resin substrate.

[0158] The first component is not particularly limited as long as it is a constituent of the resin substrate, wherein the first component is preferably a resin component constituting the resin substrate. Specifically, the first component is preferably a resin having at least one selected from the group consisting of an imide skeleton, an amide skeleton and an ester skeleton, more preferably a resin having at least an imide skeleton. More specifically, the first component is preferably a polyimide resin, a polyamide resin, a polyester resin, more preferably a polyimide resin. The adhesion of the resin substrate and the optical resin layer can be improved. Furthermore, the adhesion of the resin substrate and the optical resin layer can also be maintained after ultraviolet exposure.

[0159] The ratio of the content of the first component in each layer to the content of the first component in the resin substrate is preferably increased in the order of the optical resin layer, the first intermediate layer, the second intermediate layer and the resin substrate. It should be noted that at this time, the ratio of the content of the first component in the first intermediate layer to the content of the first component in the resin substrate is as long as it is less than the ratio of the content of the first component in the second intermediate layer to the content of the first component in the resin substrate. That is, the magnitude relationship of the above ratio is preferably optical resin layer < first intermediate layer ≤ second intermediate layer < resin substrate. The adhesion of the resin substrate and the optical resin layer can be improved. Furthermore, the adhesion of the resin substrate and the optical resin layer can also be maintained after ultraviolet exposure.

[0160] When the content of the first component in the resin substrate is set to 100%, the ratio of the content of the first component in the first intermediate layer to the content of the first component in the resin substrate can be a predetermined relationship as long as the magnitude relationship of the above ratios is in a predetermined relationship, for example, preferably 10% or more and 50% or less, more preferably 15% or more and 40% or less, and further preferably 20% or more and 30% or less. Here, if the difference in the content of the first component is large between the optical resin layer and the first intermediate layer, there is a tendency for the difference in hardness to become larger. If the difference in hardness between the optical resin layer and the first intermediate layer is large, the bending resistance may be reduced. If the above ratio is within the above range, the difference in the content of the first component can be made smaller between the optical resin layer and the first intermediate layer, and the difference in hardness can be made smaller. Therefore, the bending resistance can be improved.

[0161] Here, the ratio of the content of the first component in the first intermediate layer to the content of the first component in the resin substrate is determined by measuring the cross section of the laminate using the AFM-IR method (AFM-based Infrared Spectroscopy). When the intensity of the peak derived from the first component in the IR spectrum of the resin substrate is used as a reference, the ratio of the intensity of the peak derived from the first component in the IR spectrum of the first intermediate layer to the intensity of the peak derived from the first component in the IR spectrum of the resin substrate can be regarded as the ratio of the content of the first component in the first intermediate layer to the content of the first component in the resin substrate.

[0162] In the case of the AFM-IR method, first, characteristic peaks are confirmed from the IR spectrum of the resin substrate. The characteristic peaks derived from the resin substrate vary depending on the constituent components of the resin substrate.

[0163] For example, when the resin substrate contains a polyester resin, the peak derived from the C=O stretching vibration of the ester group appears at 1715±20 cm -1 The peak of CO stretching vibration originating from the aromatic ester group appears at 1240±20cm -1 The peak of CO stretching vibration originating from the ester group appears at 1095±20cm -1 Among them, the peak derived from the C=O stretching vibration of the ester group (1715±20cm -1 ) is easy to analyze. Therefore, it is preferred to determine the peak derived from the C=O stretching vibration of the ester group (1715±20 cm -1 It should be noted that the peak derived from the C=O stretching vibration of the ester group (1715±20 cm -1 ) is difficult to identify, the peak derived from the CO stretching vibration of the aromatic ester group (1240±20cm -1 ) intensity ratio. In addition, the peak of CO stretching vibration from aromatic ester group (1240±20cm -1 ) is also difficult to identify, the ratio of the peak intensities of the peak derived from the CO stretching vibration of the ester group (1095±20 cm-1) may be determined.

[0164] For example, when the resin substrate contains a polyamide-based resin, a peak derived from the C═O stretching vibration of an amide group appears at 1635±20 cm -1 The peak originating from the -CNH angular vibration of the amide group appears at 1540±20cm -1 The peak of CN stretching vibration originating from the amide group appears at 1265±20cm -1 Among them, the peak derived from the C=O stretching vibration of the amide group (1635±20cm -1Therefore, it is preferred to determine the peak (1635±20 cm -1 It should be noted that the peak (1635±20 cm) derived from the C=O stretching vibration of the amide group is difficult to identify. -1 ), the peak derived from the -CNH angular vibration of the amide group (1540±20cm -1 In addition, the peak (1540±20cm -1 ) is difficult to identify, the peak derived from the CN stretching vibration of the amide group (1265±20cm -1 )’s strength ratio.

[0165] For example, when the resin substrate contains a polyimide-based resin, a peak derived from the C═O stretching vibration of the imide group appears at 1725±20 cm -1 The peak originating from the CN stretching vibration of the imide group appears at 1366±20cm -1 Among them, the peak derived from the C=O stretching vibration of the imide group (1725±20cm -1 ) is easy to analyze. Therefore, it is preferable to find the peak (1725±20cm -1 It should be noted that the peak derived from the C=O stretching vibration of the imide group (1725±20 cm -1 ) is difficult to identify, the peak derived from the CN stretching vibration of the imide group (1366±20cm -1 )’s strength ratio.

[0166] AFM-IR measurement was performed using nanoIR manufactured by Anasys Instruments Inc. Specific examples of measurement conditions are shown below.

[0167] Light source: tunable pulse laser (1kHz)

[0168] AFM mode: Contact mode (when obtaining AFM-IR spectrum)

[0169] ·Measurement wave number range: 1950cm -1 ~950cm -1

[0170] Wave number resolution: 1.5cm -1

[0171] Coaverages: 512

[0172] Cumulative number of times: 3 times or more

[0173] Polarization angle: 45 degrees

[0174] In addition, the method for measuring the ratio of the content of the first component in the second intermediate layer to the content of the first component in the resin base material is also the same as described above.

[0175] In addition, the first intermediate layer preferably contains the second component constituting the optical resin layer. In the case where the optical resin layer is composed of multiple components, the first intermediate layer preferably contains at least one component of the constituent components of the optical resin layer. The adhesion between the resin substrate and the optical resin layer can be improved. In addition, the bending resistance can be improved. It should be noted that when the optical resin layer is multilayer, the second component constituting the optical resin layer is a constituent component of a layer adjacent to the first intermediate layer in the layer constituting the optical resin layer.

[0176] The second component is not particularly limited as long as it is a constituent of the optical resin layer. Among them, the second component is preferably a polymer of a polymerizable compound. In the case where the optical resin layer contains a variety of polymerizable compounds, the second component can be a polymer of at least one polymerizable compound. The adhesion between the resin substrate and the optical resin layer can be improved. In addition, the bending resistance can be improved.

[0177] The fact that the first intermediate layer contained the second component was confirmed by measuring the cross section of the laminate using the AFM-IR method (AFM-based Infrared Spectroscopy).

[0178] Here, for the laminated body with an optical resin layer having various properties disposed on the surface of a display device or a touch panel, in addition to adhesion and bending resistance, hardness characteristics are also required. In order to meet a certain degree of hardness characteristics, it is usually designed that the hardness of the optical resin layer is greater than the hardness of the resin substrate. However, in the case where the optical resin layer with high hardness is disposed in contact with the resin substrate, there is a tendency that the greater the hardness difference between the optical resin layer and the resin substrate, the lower the bending resistance. Therefore, in order to release the stress applied to the above-mentioned laminated body when bending, the balance of the hardness of each layer constituting the above-mentioned laminated body becomes important. According to the relationship between the ratio of the thickness of each layer, it can be said that the influence of the resin substrate is large. Therefore, it is considered that it is important to configure a soft intermediate layer between the resin substrate and the optical resin layer to follow the resin substrate and relieve stress. Specifically, the intermediate layer preferably has a hardness between the hardness of the resin substrate and the hardness of the optical resin layer, or the intermediate layer is preferably softer than the resin substrate and the optical resin layer. It should be noted that when the intermediate layer is softer than the resin substrate and the optical resin layer, the intermediate layer preferably has a hardness that does not reduce the hardness characteristics of the laminated body.

[0179] Therefore, when the indentation hardness of the optical resin layer is greater than the indentation hardness of the resin substrate, the indentation hardness of the first intermediate layer is preferably greater than the indentation hardness of the resin substrate and less than the indentation hardness of the optical resin layer, or the indentation hardness of the first intermediate layer is preferably less than the indentation hardness of the resin substrate and the indentation hardness of the optical resin layer, respectively. The hardness characteristics and bending resistance of the laminate become good. Among them, when the indentation hardness of the optical resin layer is greater than the indentation hardness of the resin substrate, the indentation hardness of the first intermediate layer is more preferably less than the indentation hardness of the resin substrate and the indentation hardness of the optical resin layer, respectively.

[0180] In addition, the indentation hardness of the first intermediate layer is preferably smaller than the indentation hardness of the resin substrate and the indentation hardness of the optical resin layer. The flexural resistance of the laminate becomes good.

[0181] The indentation hardness of the first intermediate layer is preferably smaller than the indentation hardness of the resin substrate and the indentation hardness of the optical resin layer, for example, preferably 100 MPa or more and 400 MPa or less, more preferably 200 MPa or more and 390 MPa or less, and further preferably 300 MPa or more and 380 MPa or less. By making the indentation hardness of the first intermediate layer within the above range, both the adhesion between the resin substrate and the optical resin layer and the bending resistance of the laminate can be improved.

[0182] As mentioned above, the intermediate layer preferably has a hardness between the hardness of the resin substrate and the hardness of the optical resin layer, or the intermediate layer is preferably softer than the resin substrate and the optical resin layer. At this time, in order to improve the followability of the intermediate layer to the resin substrate, the hardness of the intermediate layer is preferably close to the hardness of the resin substrate.

[0183] Therefore, it is preferred that the difference between the indentation hardness of the first intermediate layer and the indentation hardness of the resin substrate is smaller than the difference between the indentation hardness of the first intermediate layer and the indentation hardness of the optical resin layer. In this case, the indentation hardness of the first intermediate layer becomes a value closer to the indentation hardness of the resin substrate than the indentation hardness of the optical resin layer. Thus, both the adhesion between the resin substrate and the optical resin layer and the bending resistance of the laminate can be improved.

[0184] It is particularly preferred that the indentation hardness of the first intermediate layer is smaller than the indentation hardness of the resin substrate and the indentation hardness of the optical resin layer, and the difference between the indentation hardness of the first intermediate layer and the indentation hardness of the resin substrate is smaller than the difference between the indentation hardness of the first intermediate layer and the indentation hardness of the optical resin layer. The adhesion between the resin substrate and the optical resin layer, the hardness characteristics of the laminate, and the bending resistance of the laminate can be improved. It should be noted that, at this time, the indentation hardness of the optical resin layer must be greater than the indentation hardness of the resin substrate.

[0185] The difference between the indentation hardness of the first intermediate layer and the indentation hardness of the resin substrate may be, for example, 200 MPa or less, 150 MPa or less, less than 120 MPa, or 100 MPa or less.

[0186] Furthermore, the difference between the indentation hardness of the first intermediate layer and the indentation hardness of the optical resin layer may be 200 MPa or less, may be 150 MPa or less, may be less than 120 MPa, or may be 100 MPa or less.

[0187] The difference between the indentation hardness of the first intermediate layer and the resin substrate and the difference between the indentation hardness of the first intermediate layer and the optical resin layer are preferably less than 120 MPa, respectively. This can improve both the adhesion between the resin substrate and the optical resin layer and the bending resistance of the laminate.

[0188] The difference between the indentation hardness of the first intermediate layer and the resin substrate and the difference between the indentation hardness of the first intermediate layer and the optical resin layer is preferably 30 MPa or less, for example, to improve both the adhesion between the resin substrate and the optical resin layer and the bending resistance of the laminate.

[0189] It is particularly preferred that the indentation hardness of the first intermediate layer is less than the indentation hardness of the resin substrate and the indentation hardness of the optical resin layer, the difference between the indentation hardness of the first intermediate layer and the indentation hardness of the resin substrate is less than the difference between the indentation hardness of the first intermediate layer and the indentation hardness of the optical resin layer, the difference between the indentation hardness of the first intermediate layer and the indentation hardness of the resin substrate, and the difference between the indentation hardness of the first intermediate layer and the indentation hardness of the optical resin layer are less than 120MPa, and the difference between the indentation hardness of the first intermediate layer and the indentation hardness of the resin substrate and the difference between the indentation hardness of the first intermediate layer and the indentation hardness of the optical resin layer is less than 30MPa. It is possible to improve the adhesion between the resin substrate and the optical resin layer, the hardness characteristics of the laminate, and the bending resistance of the laminate. It should be noted that, at this time, as described above, the indentation hardness of the optical resin layer must be greater than the indentation hardness of the resin substrate.

[0190] In addition, the "indentation hardness" is a value obtained from a load-displacement curve from the load to the unloading of the indenter obtained by hardness measurement based on the nanoindentation method.

[0191] Indentation hardness (H IT) is measured using the "Hysitron TI950 TriboIndenter" manufactured by BRUKER. Specifically, first, the laminate is cut into 1 mm × 10 mm to make a block embedded with an embedding resin. Then, a slice having a uniform thickness of 50 nm or more and 100 nm or less without holes or the like is cut from the block by a general slicing method. The slices are made, for example, using the "Ultra-thin slicer EMUC7" (manufactured by Leica MicroSystems). Then, the remaining block from which the slice is cut is used as a measurement sample. Next, in the cross-section obtained by cutting the above-mentioned slice in this measurement sample, under the following measurement conditions, the indenter is vertically pressed into the center of the cross-section of the first intermediate layer. As an indenter, a Berkovich indenter (triangular pyramid, "TI-0039" manufactured by BRUKER) is used. Here, in order to avoid the influence of the resin substrate and the optical resin layer, the Berkovich indenter is pressed into the center of the thickness of the first intermediate layer at a distance of more than 300nm from the interface between the first intermediate layer and the layer adjacent to the first intermediate layer to the center of the first intermediate layer, and in order to avoid the influence of the side edge of the first intermediate layer, the Berkovich indenter is pressed into the part of the first intermediate layer at a distance of more than 500nm from the two side ends of the first intermediate layer to the center of the first intermediate layer. Then, after maintaining for a certain period of time to relax the residual stress, the load is unloaded and the maximum load after relaxation is measured. And, the maximum load P is used. max and contact projection area A p , through P max / A p Calculate the indentation hardness (H IT ). The above contact projection area A p A standard sample of fused silica ("5-0098" manufactured by BRUKER) was used, and the contact projection area of ​​the indenter tip curvature was corrected by the Oliver-Pharr method.

[0192] Indentation hardness (H IT ) is the arithmetic mean of the values ​​obtained by measuring 10 points. It should be noted that when the measured values ​​contain values ​​that deviate from the arithmetic mean by more than ±20%, the measured values ​​are excluded and re-measured. Whether there are values ​​that deviate from the arithmetic mean by more than ±20% in the measured values ​​is determined by whether the value (%) calculated by (AB) / B×100 when the measured value is set to A and the arithmetic mean is set to B is more than ±20%. Indentation hardness (H IT ) can be adjusted by the constituent components of the resin substrate and the constituent components of the optical resin layer.

[0193] (Measurement conditions of indentation hardness)

[0194] ·Press control method: displacement control method

[0195] Indentation depth: 100nm

[0196] Pressing speed: 10nm / sec

[0197] Loading time: 20 seconds

[0198] Hold time: 5 seconds

[0199] Load unloading speed: 10nm / sec

[0200] Unloading time: 20 seconds

[0201] ·Measurement temperature: 25℃

[0202] As a method for forming the first intermediate layer, for example, there is a method of applying a first intermediate layer resin composition containing a first component and an optional second component on the second intermediate layer.

[0203] The thickness of the first intermediate layer is not particularly limited as long as the adhesion between the resin substrate and the optical resin layer can be obtained, for example, preferably 1 μm or more and 5 μm or less, more preferably 2 μm or more and 5 μm or less, and further preferably 2 μm or more and 4 μm or less. When the thickness of the first intermediate layer is too thin, the adhesion between the resin substrate and the optical resin layer may become insufficient. In addition, if the thickness of the first intermediate layer is too thick, the thickness of the entire laminate becomes thicker, so there is a tendency for the bending resistance of the laminate to decrease.

[0204] Here, the thickness of the first intermediate layer is determined by dyeing the first intermediate layer in a cross section in the thickness direction of the laminate with a dye and measuring the thickness of the dyed first intermediate layer. The dye is, for example, at least one selected from the group consisting of ruthenium tetroxide, osmium tetroxide, and tungsten phosphate.

[0205] The molecular mobility of at least one amorphous part selected from the group consisting of ruthenium tetroxide, osmium tetroxide and tungsten phosphate is large, and it is easy to enter the low-density part and react. When the content of the first component in the first intermediate layer is less than the content of the first component in the resin substrate, the density of the first component constituting the resin substrate of the first intermediate layer is low, forming a low-density area. In addition, when the ratio of the content of the first component in each layer to the content of the first component in the resin substrate increases in the order of the first intermediate layer, the second intermediate layer and the resin substrate, the density of the first component constituting the resin substrate of the first intermediate layer is also low, forming a low-density area. It is believed that by attaching at least one selected from the group consisting of ruthenium tetroxide, osmium tetroxide and tungsten phosphate to the above-mentioned low-density area, the first intermediate layer can be selectively dyed.

[0206] The coloring agent is suitably selected according to the constituent of the resin substrate. In the case where the resin substrate contains a resin having at least an imide skeleton, the coloring agent is particularly preferably selected from at least one of ruthenium tetroxide and osmium tetroxide, more preferably ruthenium tetroxide. In addition, when the resin substrate contains a resin having at least an amide skeleton, the coloring agent is particularly preferably tungsten phosphate. In addition, when the resin substrate contains a resin having at least an ester skeleton, the coloring agent is particularly preferably ruthenium tetroxide.

[0207] As a method for dyeing the first intermediate layer with a dye in a cross section in the thickness direction of the laminate, the following method can be cited. First, the laminate is cut into a rectangle of 2 mm × 10 mm. Then, the sample is embedded with a resin, cured and fixed. Then, a microtome is used to cut the fixed sample in the thickness direction with a width of about 50 nm or more and 150 nm or less to make ultrathin sections. Then, the ultrathin sections are placed in a container together with the dye and sealed, and left at room temperature (25°C) for a certain period of time. In this way, the first intermediate layer is dyed with a dye. The above-mentioned standing time is not particularly limited and can be adjusted appropriately. The above-mentioned standing time is, for example, more than 10 minutes and less than 60 minutes. In addition, after standing, in order to remove the residual dye in the sample, the lid of the container can be opened and further left for a certain period of time. The standing time at this time is not particularly limited and can be adjusted appropriately. The above-mentioned standing time is, for example, more than 5 minutes and less than 30 minutes.

[0208] The thickness of the dyed first intermediate layer is an average value of thicknesses at arbitrary 10 locations measured in a cross section in the thickness direction of the laminate observed by a scanning transmission electron microscope (STEM).

[0209] 4. Second intermediate layer

[0210] The second intermediate layer in the present embodiment is disposed between the first intermediate layer and the resin base material, and contains the first component constituting the resin base material.

[0211] The second intermediate layer contains the first component constituting the resin substrate. In addition, when the resin substrate is composed of a plurality of components, the second intermediate layer only needs to contain at least one component of the components constituting the resin substrate. The first component is as described above.

[0212] When the content of the first component in the resin substrate is set to 100%, the ratio of the content of the first component in the second intermediate layer to the content of the first component in the resin substrate can be a predetermined relationship, for example, preferably 50% or more and 95% or less, more preferably 60% or more and 90% or less, and further preferably 70% or more and 80% or less. If the above ratio is too small, the second intermediate layer cannot fully absorb ultraviolet rays, and ultraviolet degradation of the resin substrate may occur. As a result, the adhesion between the resin substrate and the second intermediate layer may be reduced. If the above ratio is within the above range, the second intermediate layer can fully absorb ultraviolet rays, so the adhesion between the resin substrate and the second intermediate layer can be maintained.

[0213] In addition, the second intermediate layer preferably contains the second component constituting the optical resin layer. When the optical resin layer is composed of multiple components, the second intermediate layer preferably contains at least one component of the constituent components of the optical resin layer. The adhesion between the resin substrate and the optical resin layer can be improved. In addition, the bending resistance can be improved. It should be noted that, about the second component, as described above.

[0214] The relationship between the indentation hardness of the second intermediate layer, the indentation hardness of the resin substrate, and the indentation hardness of the optical resin layer is the same as that of the first intermediate layer, and therefore detailed description is omitted.

[0215] In the case where the indentation hardness of the optical resin layer is greater than the indentation hardness of the resin substrate, the indentation hardness of the second intermediate layer is preferably greater than the indentation hardness of the resin substrate and less than the indentation hardness of the optical resin layer, or the indentation hardness of the second intermediate layer is preferably less than the indentation hardness of the resin substrate and the indentation hardness of the optical resin layer, respectively. The hardness characteristics and bending resistance of the laminate become good. Among them, in the case where the indentation hardness of the optical resin layer is greater than the indentation hardness of the resin substrate, the indentation hardness of the second intermediate layer is more preferably less than the indentation hardness of the resin substrate and the indentation hardness of the optical resin layer, respectively.

[0216] In addition, the indentation hardness of the second intermediate layer is preferably smaller than the indentation hardness of the resin substrate and the indentation hardness of the optical resin layer. The flexural resistance of the laminate becomes good.

[0217] The indentation hardness of the second intermediate layer is preferably smaller than the indentation hardness of the resin substrate and the indentation hardness of the optical resin layer, for example, preferably 100 MPa or more and 400 Pa or less, more preferably 200 MPa or more and 390 MPa or less, and further preferably 300 MPa or more and 380 MPa or less. By making the indentation hardness of the second intermediate layer within the above range, both the adhesion between the resin substrate and the optical resin layer and the bending resistance of the laminate can be improved.

[0218] Among them, it is preferred that the indentation hardness of the first intermediate layer satisfies the preferred relationship with the indentation hardness of the resin substrate and the indentation hardness of the optical resin layer, and the indentation hardness of the second intermediate layer satisfies the preferred relationship with the indentation hardness of the resin substrate and the indentation hardness of the optical resin layer.

[0219] It should be noted that the method for measuring the indentation hardness of the second intermediate layer is the same as the method for measuring the indentation hardness of the first intermediate layer described above.

[0220] Here, in the measurement of the indentation hardness of the second intermediate layer, when the indenter is pressed vertically into the center of the cross-section of the second intermediate layer, in order to avoid the influence of the resin substrate and the optical resin layer, the Berkovitch indenter is pressed into the center of the thickness of the second intermediate layer at a distance of more than 300nm from the interface between the second intermediate layer and the layer adjacent to the second intermediate layer to the center side of the second intermediate layer, and in order to avoid the influence of the side edge of the second intermediate layer, the Berkovitch indenter is pressed into a portion of the second intermediate layer at a distance of more than 500nm from both side ends of the second intermediate layer to the center side of the second intermediate layer.

[0221] As a method for forming the second intermediate layer, for example, there is a method of applying a second intermediate layer resin composition containing a first component and an optional second component on a resin substrate.

[0222] The thickness of the second intermediate layer is not particularly limited as long as the adhesion between the resin substrate and the optical resin layer can be obtained, for example, preferably 1 μm or more and 5 μm or less, more preferably 2 μm or more and 5 μm or less, and further preferably 2 μm or more and 4 μm or less. When the thickness of the second intermediate layer is too thin, the adhesion between the resin substrate and the optical resin layer may become insufficient. In addition, if the thickness of the second intermediate layer is too thick, the thickness of the entire laminate becomes thicker, so there is a tendency for the bending resistance of the laminate to decrease.

[0223] Here, the method for measuring the thickness of the second intermediate layer is the same as the method for measuring the thickness of the first intermediate layer described above.

[0224] When the ratio of the content of the first component in each layer to the content of the first component in the resin substrate increases in the order of the first intermediate layer, the second intermediate layer, and the resin substrate, the density of the first component constituting the resin substrate in the first intermediate layer and the second intermediate layer is low, forming a low-density region. It is believed that by attaching at least one selected from the group consisting of ruthenium tetroxide, osmium tetroxide, and tungsten phosphate to the low-density region, the first intermediate layer and the second intermediate layer can be selectively dyed.

[0225] At this time, the first intermediate layer and the second intermediate layer have different contents of the first component constituting the resin substrate, and therefore the density of the constituent components of the resin substrate is different. Therefore, it is believed that the dyeing concentration is different in the first intermediate layer and the second intermediate layer. Therefore, the interface between the first intermediate layer and the second intermediate layer can be observed.

[0226] It should be noted that when the first intermediate layer and the second intermediate layer are dyed with a dye, the interface between the first intermediate layer and the second intermediate layer may not be clear. Figure 2 As shown in FIG. 1 , when the total thickness of the first intermediate layer 3 and the second intermediate layer 4 is set to T, when the content of the first component constituting the resin substrate is different in the region of thickness T / 3 from the optical resin layer 2 side and the region of thickness T / 3 from the resin substrate 5 side, the laminated body of the present embodiment is also regarded as having the first intermediate layer and the second intermediate layer. The difference in the content of the first component constituting the resin substrate in the region of thickness T / 3 from the optical resin layer side and the region of thickness T / 3 from the resin substrate side can be confirmed by comparing the ratio of the content of the first component in each region to the content of the first component in the resin substrate.

[0227] 5. Other layers

[0228] The laminated body of the present embodiment may have other layers in addition to the above-mentioned resin substrate, optical resin layer, first intermediate layer, and second intermediate layer.

[0229] (1) Second optical resin layer

[0230] The laminated body of this embodiment may have a second optical resin layer on the surface of the resin substrate opposite to the optical resin layer. The second optical resin layer is the same as the above-mentioned optical resin layer.

[0231] (2) The third and fourth intermediate layers

[0232] In this embodiment, the third intermediate layer, the fourth intermediate layer and the second optical resin layer can be sequentially arranged from the resin substrate side on the surface of the resin substrate opposite to the optical resin layer. The third intermediate layer is the same as the second intermediate layer. In addition, the fourth intermediate layer is the same as the first intermediate layer. For example, when the laminate is arranged on the surface of the display device, the laminate is arranged in a manner that the optical resin layer becomes the observer side and the second optical resin layer becomes the display panel side. In this case, the first intermediate layer and the second intermediate layer can suppress the degradation of the resin substrate caused by external light, and maintain the adhesion of the resin substrate and the optical resin layer. In addition, the third intermediate layer and the fourth intermediate layer can suppress the degradation of the resin substrate caused by the illumination light of the display device, and maintain the adhesion of the resin substrate and the second optical resin layer.

[0233] (3) Adhesive layer for pasting

[0234] The laminate of this embodiment may have a bonding adhesive layer on the surface of the resin substrate opposite to the optical resin layer. The laminate may be bonded to, for example, a display panel via the bonding adhesive layer.

[0235] The adhesive used in the bonding adhesive layer is not particularly limited as long as it is transparent and can bond the laminate to a display panel, etc. For example, thermosetting adhesives, ultraviolet curing adhesives, two-component curing adhesives, hot melt adhesives, and pressure-sensitive adhesives (so-called adhesives) can be mentioned.

[0236] The thickness of the adhesive layer for pasting is preferably, for example, 10 μm or more and 100 μm or less, more preferably 25 μm or more and 80 μm or less, and further preferably 40 μm or more and 60 μm or less. If the thickness of the adhesive layer for pasting is too thin, it may not be possible to fully bond the laminate to the display panel, etc. In addition, when the thickness of the adhesive layer for pasting is too thick, flexibility is sometimes impaired.

[0237] As the adhesive layer for pasting, for example, an adhesive film can be used. Alternatively, for example, an adhesive composition can be applied on a support or a resin substrate to form the adhesive layer for pasting.

[0238] 6. Characteristics of laminated body

[0239] The total light transmittance of the laminate of the present embodiment is, for example, preferably 85% or more, more preferably 88% or more, and even more preferably 90% or more. As the total light transmittance is high, the transparency becomes good.

[0240] Here, the total light transmittance of the laminate is measured in accordance with JIS K7361-1: 1999. For example, a haze meter HM150 manufactured by Murakami Color Research Laboratory is used.

[0241] The haze of the laminate of the present embodiment is, for example, preferably 5% or less, more preferably 2% or less, and further preferably 1% or less. As the haze is low, the transparency becomes good.

[0242] Here, the haze of the laminate is measured in accordance with JIS K7136: 2000. For example, a haze meter HM150 manufactured by Murakami Color Research Laboratory is used.

[0243] The laminate of the present embodiment preferably has bending resistance. Specifically, when the laminate is subjected to a dynamic bending test described below, it is preferred that the laminate does not crack, break or peel.

[0244] The dynamic bending test was conducted as follows. First, a laminate of 20 mm × 100 mm in size was prepared. Figure 3As shown in (a), the short side 1C of the laminate 1 and the short side 1D facing the short side 1C are fixed by the fixing parts 51 arranged in parallel. Figure 3 As shown in (a), the fixing portion 51 can slide in the horizontal direction. Figure 3 As shown in (b), the fixing portions 51 are moved in a manner close to each other, thereby deforming the laminate 1 in a folded manner, and then, as shown in Figure 3 As shown in (c), the fixing portion 51 is moved to a position where the interval d between the two opposing short sides 1C and 1D fixed by the fixing portion 51 of the laminate 1 reaches a predetermined value, and then the fixing portion 51 is moved in the reverse direction to eliminate the deformation of the laminate 1. Figure 3 By moving as shown in (a) to 3(c), the laminate 1 can be folded 180°. In addition, by performing a dynamic bending test in a manner such that the bent portion 1E of the laminate 1 does not protrude from the lower end of the fixing portion 51, and by controlling the interval when the fixing portion 51 is closest, the interval d between the two opposing short sides 1C and 1D of the laminate 1 can be set to a specified value. For example, when the interval d between the short sides 1C and 1D is 10 mm, the outer diameter of the bent portion 1E is regarded as 10 mm. In the dynamic bending test, for example, a durability testing machine (product name "DLDMLH-FS", manufactured by Yuasa System Instruments) is used.

[0245] In the laminate, it is preferred that no crack, break or peeling occurs when a dynamic bending test is repeated 200,000 times in which the laminate 1 is folded 180° so that the interval d between the opposing short sides 1C and 1D is 10 mm. In particular, it is preferred that no crack, break or peeling occurs when a dynamic bending test is repeated 200,000 times in which the laminate 1 is folded 180° so that the interval d between the opposing short sides 1C and 1D is 8 mm.

[0246] In the dynamic bending test, the laminate may be folded so that the optical resin layer faces outside or inside. In either case, it is preferred that the laminate does not crack, break or peel.

[0247] Here, in the dynamic bending test, "fracture" refers to the phenomenon that cracks are generated in the laminate. In addition, "breakage" refers to the phenomenon that the laminate is completely split into two. In addition, "peeling" refers to the phenomenon that any layer constituting the laminate is peeled off or floated.

[0248] In this embodiment, the degradation of the resin substrate caused by ultraviolet rays can be suppressed, and the adhesion between the resin substrate and the optical resin layer can be maintained. Specifically, after the laminate is subjected to the accelerated weathering test based on the following JIS K5600-7-8:1999, when the adhesion test based on the checkerboard tape method based on JIS K5400-8.5.2 is performed, the number of remaining grids out of 100 grids is preferably 90 or more, more preferably 95 or more, and further preferably 100.

[0249] (Conditions that promote weathering test)

[0250] Procedure: Method A involves exposure to water vapor condensation

[0251] UV light: Type 2 UVA (340)

[0252] Irradiation: irradiance 0.63W / m 2 , temperature 23±5℃, black panel temperature 60±3℃, irradiation time 4 hours

[0253] Water vapor condensation: Black panel temperature 50±3℃, water condensation time 4 hours

[0254] 1 cycle: The above irradiation and the above water vapor condensation are performed in sequence as 1 cycle

[0255] Number of cycles: 12 cycles

[0256] In addition, in the accelerated weathering test, ultraviolet rays were irradiated from the surface of the optical resin layer side of the laminate.

[0257] In addition, the adhesion test based on the checkerboard tape method of JIS K5400-8.5.2 was carried out by the following method. First, a cutter was used to cut a checkerboard-like cut at intervals of 1 mm in a manner that the optical resin layer side of the laminate reached the surface of the resin substrate to form 100 grids. Then, a transparent tape (made by NICHIBAN) was pasted on the above grid and peeled off, and it was repeated 5 times. Then, the state of the grid was observed visually.

[0258] 7. Other aspects of the laminate

[0259] The thickness of the laminate of the present embodiment is, for example, preferably 10 μm to 500 μm, more preferably 20 μm to 400 μm, and further preferably 30 μm to 300 μm. When the thickness of the laminate is within the above range, flexibility can be improved.

[0260] The laminate of this embodiment can be used as a front panel arranged on the observer side of the display device. In addition, the laminate of this embodiment can be used as a front panel arranged on the surface of the touch panel member. Among them, the laminate of this embodiment can be suitable for the front panel of a flexible display device such as a foldable display, a rollable display, and a bendable display. In particular, the laminate of this embodiment has good bending resistance, so it can be suitable for the front panel of a foldable display.

[0261] The laminate of this embodiment can be used as a front panel of a display device such as a smartphone, a tablet terminal, a wearable terminal, a personal computer, a television, a digital signage, a public information display (PID), or a car display.

[0262] II. Second Embodiment

[0263] A second embodiment of the laminated body in the present disclosure includes an optical resin layer, an intermediate layer, and a resin substrate in this order, and the intermediate layer contains a first component constituting the resin substrate and a second component constituting the optical resin layer.

[0264] Figure 4 : is a schematic cross-sectional view showing an example of a laminated body according to this embodiment. Figure 4 As shown, the laminate 1B includes an optical resin layer 2, an intermediate layer 6, and a resin base material 5 in this order. The intermediate layer 6 contains a first component constituting the resin base material 5 and a second component constituting the optical resin layer 2.

[0265] In this embodiment, by disposing an intermediate layer containing a first component constituting the resin substrate and a second component constituting the optical resin layer between the optical resin layer and the resin substrate, the adhesion between the optical resin layer and the resin substrate can be improved.

[0266] Here, in the laminate, when ultraviolet rays are irradiated from the surface on the optical resin layer side of the laminate, in the resin substrate, degradation proceeds from the surface on the optical resin layer side of the resin substrate. In the present embodiment, the intermediate layer disposed between the optical resin layer and the resin substrate contains the first component constituting the resin substrate, and therefore, even if the first component contained in the intermediate layer degrades due to ultraviolet rays, degradation of the resin substrate due to ultraviolet rays can be suppressed. Therefore, ultraviolet degradation of the resin substrate can be suppressed, and adhesion between the optical resin layer and the resin substrate can be maintained.

[0267] Thus, in the present embodiment, even if the ultraviolet light absorber is not used, the decrease in the adhesion between the optical resin layer and the resin substrate caused by the ultraviolet light degradation of the resin substrate can be suppressed. Therefore, the hardness characteristics of the optical resin layer can be suppressed to be reduced as in the past because the optical resin layer contains the ultraviolet light absorber. In addition, the bending resistance can be suppressed to be reduced as in the past because the ultraviolet light absorber is biased to the surface side of the optical resin layer side of the resin substrate.

[0268] Hereinafter, each structure of the laminated body of this embodiment will be described.

[0269] 1. Resin substrate

[0270] The material and thickness of the resin substrate are the same as those of the resin substrate in the laminated body of the first embodiment.

[0271] The indentation hardness of the resin substrate is preferably greater than the indentation hardness of the intermediate layer. This improves the bending resistance of the laminate.

[0272] The indentation hardness of the resin substrate is the same as the indentation hardness of the resin substrate in the laminated body of the first embodiment described above.

[0273] 2. Optical resin layer

[0274] The material, thickness, structure, and formation method of the optical resin layer are the same as those of the optical resin layer in the laminated body of the first embodiment.

[0275] The indentation hardness of the optical resin layer is preferably greater than the indentation hardness of the resin substrate. This improves the hardness characteristics of the laminate.

[0276] The indentation hardness of the optical resin layer is preferably greater than that of the intermediate layer. This improves the hardness characteristics and bending resistance of the laminate.

[0277] The indentation hardness of the optical resin layer is the same as the indentation hardness of the optical resin layer in the laminated body of the first embodiment described above.

[0278] 3. Middle layer

[0279] The intermediate layer in the present embodiment is disposed between the optical resin layer and the resin substrate, and contains the first component constituting the resin substrate and the second component constituting the optical resin layer.

[0280] The first component and the second component are respectively the same as the first component and the second component in the laminated body of the first embodiment described above.

[0281] The ratio of the content of the first component in each layer to the content of the first component in the resin substrate is preferably increased in the order of the optical resin layer, the intermediate layer and the resin substrate. That is, the magnitude relationship of the above ratio is preferably optical resin layer < intermediate layer < resin substrate. The adhesion of the resin substrate and the optical resin layer can be improved. Furthermore, the adhesion of the resin substrate and the optical resin layer can also be maintained after ultraviolet exposure.

[0282] When the content of the first component in the resin substrate is set to 100%, the ratio of the content of the first component in the intermediate layer to the content of the first component in the resin substrate can be a ratio that is in a prescribed relationship, for example, greater than 10% and less than 90%, greater than 15% and less than 60%, or greater than 20% and less than 40%.

[0283] The relationship between the indentation hardness of the intermediate layer, the indentation hardness of the resin substrate, and the indentation hardness of the optical resin layer is the same as the relationship between the indentation hardness of the first intermediate layer, the indentation hardness of the resin substrate, and the optical resin layer in the laminate of the first embodiment described above, so detailed description is omitted.

[0284] Furthermore, the indentation hardness of the intermediate layer is preferably smaller than the indentation hardness of the resin substrate and the indentation hardness of the optical resin layer. The flexural resistance of the laminated body is improved.

[0285] The indentation hardness of the intermediate layer is the same as the indentation hardness of the first intermediate layer in the laminated body of the first embodiment described above.

[0286] As a method for forming the intermediate layer, for example, there is a method of applying a resin composition for an intermediate layer containing a first component and an optional second component on a resin substrate.

[0287] The thickness of the intermediate layer is the same as the thickness of the intermediate layer in the laminated body of the first embodiment described above.

[0288] 4. Other layers

[0289] The laminated body of the present embodiment may have other layers in addition to the above-mentioned resin substrate, optical resin layer, and intermediate layer.

[0290] (1) Second optical resin layer

[0291] The laminated body of this embodiment may have a second optical resin layer on the surface of the resin substrate opposite to the optical resin layer. The second optical resin layer is the same as the above-mentioned optical resin layer.

[0292] (2) 5th intermediate layer

[0293] The laminate of the present embodiment may have a fifth intermediate layer between the resin substrate and the second optical resin layer. The fifth intermediate layer is the same as the above intermediate layer. For example, when the laminate is disposed on the surface of a display device, the laminate is disposed in a manner such that the optical resin layer becomes the observer side and the second optical resin layer becomes the display panel side. In this case, the intermediate layer can suppress the deterioration of the resin substrate caused by external light and maintain the adhesion of the resin substrate and the optical resin layer. In addition, the fifth intermediate layer can suppress the deterioration of the resin substrate caused by the illumination light of the display device and maintain the adhesion of the resin substrate and the second optical resin layer.

[0294] (3) Adhesive layer for pasting

[0295] The laminate of the present embodiment may include a pasting adhesive layer on the surface of the resin substrate opposite to the optical resin layer. The pasting adhesive layer is the same as the pasting adhesive layer in the laminate of the first embodiment.

[0296] 5. Characteristics of laminated body

[0297] The characteristics of the laminated body of this embodiment are the same as those of the laminated body of the above-mentioned first embodiment.

[0298] 6. Other aspects of the laminate

[0299] The thickness and application of the laminated body of this embodiment are the same as those of the laminated body of the first embodiment.

[0300] III. Third Embodiment

[0301] The third embodiment of the laminate in the present disclosure is a laminate having an optical resin layer, an intermediate layer and a resin substrate in sequence, wherein the intermediate layer contains the first component constituting the resin substrate, and after the laminate is subjected to an accelerated weathering test based on the following JIS K5600-7-8:1999, an adhesion test based on the checkerboard tape method based on JIS K5400-8.5.2 is conducted, and the number of grids remaining in 100 grids is greater than 90.

[0302] (Conditions that promote weathering test)

[0303] Procedure: Method A involves exposure to water vapor condensation

[0304] UV light: Type 2 UVA (340)

[0305] Irradiation: irradiance 0.63W / m 2 , temperature 23±5℃, black panel temperature 60±3℃, irradiation time 4 hours

[0306] Water vapor condensation: Black panel temperature 50±3℃, water condensation time 4 hours

[0307] 1 cycle: The above irradiation and the above water vapor condensation are performed in sequence as 1 cycle

[0308] Number of cycles: 12 cycles

[0309] Figure 4 : is a schematic cross-sectional view showing an example of a laminated body according to this embodiment. Figure 4 As shown, the laminate 1B has an optical resin layer 2, an intermediate layer 6, and a resin substrate 5 in this order. The intermediate layer 6 contains the first component constituting the resin substrate 5. In addition, in the laminate 1B, after the accelerated weathering test, when the adhesion test using the checkerboard tape method is performed, the number of remaining grids in 100 grids is greater than a specified value.

[0310] In the present embodiment, by disposing the intermediate layer containing the first component constituting the resin substrate between the optical resin layer and the resin substrate, it is possible to improve the adhesion between the optical resin layer and the resin substrate.

[0311] Here, in the laminate, when ultraviolet rays are irradiated from the surface on the optical resin layer side of the laminate, in the resin substrate, degradation occurs from the surface on the optical resin layer side of the resin substrate. In the present embodiment, the intermediate layer disposed between the optical resin layer and the resin substrate contains the first component constituting the resin substrate, so even if the first component contained in the intermediate layer degrades due to ultraviolet rays, degradation of the resin substrate due to ultraviolet rays can be suppressed. In addition, in the laminate of the present embodiment, after the above-mentioned accelerated weathering test is performed, when the above-mentioned adhesion test using the checkerboard tape method is performed, the number of grids remaining in 100 grids is greater than the specified value, so the adhesion after the accelerated weathering test is excellent. Therefore, ultraviolet degradation of the resin substrate can be suppressed, and the adhesion of the optical resin layer and the resin substrate can be maintained at a high level.

[0312] Thus, in the present embodiment, even if the ultraviolet light absorber is not used, the decrease in the adhesion between the optical resin layer and the resin substrate caused by the ultraviolet light degradation of the resin substrate can be suppressed. Therefore, the hardness characteristics of the optical resin layer can be suppressed to be reduced as in the past because the optical resin layer contains the ultraviolet light absorber. In addition, the bending resistance can be suppressed to be reduced as in the past because the ultraviolet light absorber is biased to the surface side of the optical resin layer side of the resin substrate.

[0313] Hereinafter, each structure of the laminated body of this embodiment will be described.

[0314] 1. Resin substrate

[0315] The material and thickness of the resin substrate are the same as those of the resin substrate in the laminated body of the first embodiment.

[0316] The indentation hardness of the resin substrate is preferably greater than the indentation hardness of the intermediate layer. This improves the bending resistance of the laminate.

[0317] The indentation hardness of the resin substrate is the same as the indentation hardness of the resin substrate in the laminated body of the first embodiment described above.

[0318] 2. Optical resin layer

[0319] The material, thickness, structure, and formation method of the optical resin layer are the same as those of the optical resin layer in the laminated body of the first embodiment.

[0320] The indentation hardness of the optical resin layer is preferably greater than the indentation hardness of the resin substrate. This improves the hardness characteristics of the laminate.

[0321] The indentation hardness of the optical resin layer is preferably greater than that of the intermediate layer. This improves the hardness characteristics and bending resistance of the laminate.

[0322] The indentation hardness of the optical resin layer is the same as the indentation hardness of the optical resin layer in the laminated body of the first embodiment described above.

[0323] 3. Middle layer

[0324] The intermediate layer in the present embodiment is disposed between the optical resin layer and the resin substrate, and contains the first component constituting the resin substrate.

[0325] The first component is the same as the first component in the laminated body of the above-mentioned first embodiment.

[0326] The ratio of the content of the first component in each layer to the content of the first component in the resin substrate is preferably increased in the order of the optical resin layer, the intermediate layer and the resin substrate. That is, the magnitude relationship of the above ratio is preferably optical resin layer < intermediate layer < resin substrate. The adhesion of the resin substrate and the optical resin layer can be improved. Furthermore, the adhesion of the resin substrate and the optical resin layer can also be maintained after ultraviolet exposure.

[0327] When the content of the first component in the resin substrate is set to 100%, the ratio of the content of the first component in the intermediate layer to the content of the first component in the resin substrate is the same as the ratio of the content of the first component in the intermediate layer in the laminate of the above-mentioned second embodiment to the content of the first component in the resin substrate.

[0328] In addition, the intermediate layer preferably contains the second component constituting the optical resin layer. When the optical resin layer is composed of multiple components, the intermediate layer preferably contains at least one component of the constituent components of the optical resin layer. The adhesion between the resin substrate and the optical resin layer can be improved. It should be noted that when the optical resin layer is multilayer, the second component constituting the optical resin layer is a constituent component of a layer adjacent to the intermediate layer in the layer constituting the optical resin layer.

[0329] The second component is the same as the second component in the laminated body of the above-mentioned first embodiment.

[0330] The relationship between the indentation hardness of the intermediate layer, the indentation hardness of the resin substrate, and the indentation hardness of the optical resin layer is the same as the relationship between the indentation hardness of the first intermediate layer, the indentation hardness of the resin substrate, and the optical resin layer in the laminate of the first embodiment described above, so detailed description is omitted.

[0331] In addition, the indentation hardness of the intermediate layer is preferably smaller than the indentation hardness of the resin substrate and the indentation hardness of the optical resin layer. The flexural resistance of the laminated body becomes good.

[0332] The indentation hardness of the intermediate layer is the same as the indentation hardness of the first intermediate layer in the laminated body of the first embodiment described above.

[0333] As a method for forming the intermediate layer, for example, there is a method of applying a resin composition for an intermediate layer containing a first component and an optional second component on a resin substrate.

[0334] The thickness of the intermediate layer is the same as the thickness of the intermediate layer in the laminated body of the first embodiment described above.

[0335] 4. Other layers

[0336] The laminate of the present embodiment may also have other layers in addition to the above-mentioned resin substrate, optical resin layer and intermediate layer. As other layers, for example, the second optical resin layer, the fifth intermediate layer and the adhesive layer for pasting can be cited. About the second optical resin layer, the fifth intermediate layer and the adhesive layer for pasting, they are respectively the same as the second optical resin layer, the fifth intermediate layer and the adhesive layer for pasting in the laminate of the second embodiment described above.

[0337] 5. Characteristics of laminated body

[0338] The characteristics of the laminated body of this embodiment are the same as those of the laminated body of the above-mentioned first embodiment.

[0339] 6. Other aspects of the laminate

[0340] The thickness and application of the laminated body of this embodiment are the same as those of the laminated body of the first embodiment.

[0341] B. Touch panel components

[0342] The touch panel member in the present disclosure includes the above-mentioned laminated body on the surface.

[0343] In the touch panel member having the laminate on the surface, the laminate is arranged so that the resin substrate faces the touch panel member side and the optical resin layer faces the user side.

[0344] There is no particular limitation on the method of configuring the laminate on the surface of the touch panel member, and for example, a method of attaching the laminate to the touch panel member via an adhesive layer can be cited. In addition, the resin substrate constituting the laminate can also serve as a substrate layer constituting the touch panel member. In this case, an electrode constituting the touch panel member can be formed on the surface of the resin substrate side of the laminate.

[0345] The type of the touch panel member is not particularly limited, and examples thereof include electrostatic capacitance type, resistance film type, optical type, ultrasonic type, and electromagnetic induction type.

[0346] C. Display device

[0347] The display device in the present disclosure includes a display panel and the stacked body disposed on the viewer side of the display panel.

[0348] Figure 5 is a schematic cross-sectional view showing an example of a display device in the present disclosure. Figure 5 As shown, the display device 10 includes a display panel 11 and a laminate 1 disposed on the viewer side of the display panel 11. In the display device 10, the laminate 1 and the display panel 11 can be bonded together via, for example, a bonding adhesive layer 7 of the laminate 1.

[0349] When the laminate is disposed on the surface of a display panel, Figure 5 As shown, the laminate 1 is arranged so that the resin substrate 5 faces the display panel 11 side and the optical resin layer 2 faces the viewer side.

[0350] The method of disposing the laminate on the surface of the display panel is not particularly limited, and examples thereof include a method of bonding the laminate to the display panel via an adhesive layer.

[0351] Examples of the display panel include display panels used in display devices such as organic EL display devices and liquid crystal display devices.

[0352] The display device may include a touch panel member between the display panel and the laminated body.

[0353] Among them, the display device in the present disclosure is preferably a flexible display device such as a foldable display, a rollable display, a bendable display, etc.

[0354] In addition, the display device in the present disclosure is preferably foldable. That is, the display device in the present disclosure is preferably a foldable display. The display device in the present disclosure has good bending resistance and is suitable as a foldable display.

[0355] It should be noted that the present disclosure is not limited to the above-mentioned embodiments. The above-mentioned embodiments are illustrative, and any other embodiments having substantially the same structure as the technical concept described in the claims of the present disclosure and having the same effects are included in the technical scope of the present disclosure.

[0356] Example

[0357] Hereinafter, examples and comparative examples are shown to further illustrate the present disclosure.

[0358] [Example 1]

[0359] (1) Preparation of resin substrate

[0360] (1-1) Synthesis of polyimide

[0361] A 500 mL detachable flask was purged with nitrogen, and a solution containing 398.58 g of dehydrated dimethylacetamide (DMAc) and 36.65 g (114.4 mmol) of 2,2'-bis(trifluoromethyl)benzidine (TFMB) was dissolved to a liquid temperature of 30 ° C, and then 50.54 g (113.8 mmol) of 4,4'-(hexafluoroisopropylidene) diphthalic anhydride (6FDA) was slowly added in a manner that the temperature rose to below 2 ° C, and stirred for 3 hours with a mechanical stirrer to obtain a polyamic acid solution. Next, 1.73 g (79.1 mmol) of pyridine and 55.85 g (547.1 mmol) of acetic anhydride as a catalyst were added, and stirred for further 3 hours to obtain a polyimide solution. Then, 233.65 g of 2-propanol (IPA) was slowly added to the solution cooled to room temperature to obtain a slightly turbid solution. 467.5 g of IPA was added to the turbid solution at once to obtain a white slurry. The slurry was filtered, washed with IPA five times, and dried in an oven heated to 100° C. under reduced pressure for 6 hours to obtain 66.1 g of polyimide powder A.

[0362] (1-2) Production of polyimide film

[0363] N,N-dimethylacetamide (DMAc) was added to polyimide powder A to prepare a polyimide resin composition 1 having a solid content of 12%. Using the polyimide resin composition 1, the following steps (1) to (2) were performed to produce a single-layer polyimide film having a thickness of 77.5 μm. (1) The polyimide resin composition 1 was applied on a glass plate, dried in a circulation oven at 120°C for 10 minutes, cooled to 25°C, and the polyimide resin coating was peeled off. (2) The peeled polyimide resin coating was cut into a size of 150 mm × 200 mm.

[0364] Two metal frames (external dimensions 150 mm × 200 mm, internal dimensions 130 mm × 180 mm) were used to clamp the cut polyimide resin coating film, and the metal frame and the polyimide resin coating film were fixed by a fixing fixture. The fixed polyimide resin coating film was heated to 300° C. at a heating rate of 10° C. / min in a circulation oven under a nitrogen flow (oxygen concentration of 100 ppm or less), maintained at 300° C. for 1 hour, and then cooled to 25° C. to produce a single-layer polyimide film.

[0365] (2) Formation of the second intermediate layer

[0366] The respective components were mixed so as to have the composition shown below to prepare a resin composition for a second intermediate layer.

[0367] <Composition of the Second Intermediate Layer Resin Composition>

[0368] 4.8 parts by mass of a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (M403, manufactured by Toagosei Co., Ltd.)

[0369] · Dipentaerythritol EO-modified hexaacrylate (A-DPH-6E, manufactured by Shin-Nakamura Chemical Co., Ltd.) 4.8 parts by mass

[0370] 40.5 parts by mass of the above polyimide

[0371] · Photopolymerization initiator (Irg184) 4 parts by mass

[0372] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.05 parts by mass

[0373] Solvent (MIBK) 150 parts by mass

[0374] The second intermediate layer resin composition was applied on the resin substrate, dried at 70°C for 1 minute, and then heated at 200 mJ / cm2 under a nitrogen flow. 2 The film was cured by irradiating with ultraviolet light at an exposure dose of , thereby forming a second intermediate layer with a thickness of about 2.5 μm.

[0375] (3) Formation of the first intermediate layer

[0376] The respective components were blended so as to have the composition shown below to prepare a first intermediate layer resin composition.

[0377] <Composition of the first intermediate layer resin composition>

[0378] · A mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (M403, manufactured by Toagosei Co., Ltd.) 18.2 parts by mass

[0379] · Dipentaerythritol EO-modified hexaacrylate (A-DPH-6E, manufactured by Shin-Nakamura Chemical Co., Ltd.) 18.2 parts by mass

[0380] 13.5 parts by mass of the above polyimide

[0381] · Photopolymerization initiator (Irg184) 4 parts by mass

[0382] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.05 parts by mass

[0383] Solvent (MIBK) 150 parts by mass

[0384] The first intermediate layer resin composition was applied on the second intermediate layer, dried at 70°C for 1 minute, and then heated at 200 mJ / cm2 under a nitrogen stream. 2 The film was cured by irradiating with ultraviolet light at an exposure amount of , thereby forming a first intermediate layer with a thickness of about 2.6 μm.

[0385] (4) Formation of optical resin layer

[0386] The respective components were mixed so as to have the composition shown below to prepare a resin composition for an optical resin layer.

[0387] <Composition of Resin Composition for Optical Resin Layer>

[0388] · A mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (M403, manufactured by Toagosei Co., Ltd.) 25 parts by mass

[0389] · Dipentaerythritol EO-modified hexaacrylate (A-DPH-6E, manufactured by Shin-Nakamura Chemical Co., Ltd.) 25 parts by mass

[0390] · Photopolymerization initiator (Irg184) 4 parts by mass

[0391] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by mass

[0392] Solvent (MIBK) 150 parts by mass

[0393] The resin composition for the optical resin layer was applied onto the first intermediate layer, dried at 70°C for 1 minute, and then heated at 400 mJ / cm2 under a nitrogen stream. 2 The resultant was cured by irradiating with ultraviolet light at an exposure amount of 1000 μm to form an optical resin layer having a thickness of about 2.5 μm. Thus, a laminate was obtained.

[0394] [Examples 2 to 4, Examples 6 to 16]

[0395] The laminate was prepared in the same manner as in Example 1 except that the compositions of the resin composition for the optical resin layer, the resin composition for the first intermediate layer, and the resin composition for the second intermediate layer, and the thicknesses of the optical resin layer, the first intermediate layer, the second intermediate layer, and the resin substrate were changed as shown in Table 1. The composition of each resin composition was prepared in such a manner that the ratio of the content of the polyimide component to the solid content other than the solvent was the ratio shown in Table 1.

[0396] [Example 5]

[0397] A resin composition for an optical resin layer having the following composition was prepared, and a laminate was produced in the same manner as in Example 1 except that the thicknesses of the optical resin layer, the first intermediate layer, and the second intermediate layer were changed as shown in Table 1.

[0398] <Composition of Resin Composition for Optical Resin Layer>

[0399] · A mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (M403, manufactured by Toagosei Co., Ltd.) 25 parts by mass

[0400] · Dipentaerythritol EO-modified hexaacrylate (A-DPH-6E, manufactured by Shin-Nakamura Chemical Co., Ltd.) 25 parts by mass

[0401] · 50 parts by mass of irregular silicon dioxide fine particles (average particle size 25 nm, manufactured by JGC Catalysts & Chemicals Co., Ltd.)

[0402] · Photopolymerization initiator (Irg184) 4 parts by mass

[0403] Fluorine-based leveling agent (F568, manufactured by DIC Corporation) 0.2 parts by mass

[0404] Solvent (MIBK) 300 parts by mass

[0405] [Examples 17 to 19]

[0406] The laminate was prepared in the same manner as in Example 1 except that the second intermediate layer was not formed, and the compositions of the resin composition for the optical resin layer and the resin composition for the intermediate layer, and the thicknesses of the optical resin layer, the intermediate layer, and the resin substrate were changed as shown in Table 1. The composition of each resin composition was prepared in such a manner that the ratio of the content of the polyimide component to the solid content other than the solvent was the ratio shown in Table 1. In addition, the components contained in the resin composition for the intermediate layer were the same as those contained in the resin composition for the first intermediate layer of Example 1.

[0407] [Comparative Example 1]

[0408] A laminate was produced in the same manner as in Example 1 except that the first intermediate layer and the second intermediate layer were not formed and the thicknesses of the resin substrate and the optical resin layer were changed as shown in Table 1.

[0409] [Comparative Example 2]

[0410] A laminate was obtained in the same manner as in Comparative Example 1 except that an ultraviolet absorber (DAINSORB P6, manufactured by Yamato Chemicals Co., Ltd.) was added to the resin composition for an optical resin layer used in Example 1 so that the content of the ultraviolet absorber was 8% by mass based on the solid content.

[0411] [Comparative Example 3]

[0412] First, in the same manner as in Example 1, a single-layer polyimide film having a thickness of 80.1 μm was prepared.

[0413] In addition, a polyimide resin composition 2 having a solid content of 12% was prepared, wherein the polyimide powder A was 11.64 parts by mass, an ultraviolet absorber (DAINSORB P6, manufactured by Yamato Chemical) was 0.36 parts by mass, and N,N-dimethylacetamide (DMAc) was 80 parts by mass. The polyimide resin composition 2 was applied to the polyimide film, dried in a circulation oven at 120°C for 10 minutes, and then cooled to 25°C. The polyimide resin coating was heated to 300°C at a heating rate of 10°C / min in a circulation oven under a nitrogen flow (oxygen concentration of 100 ppm or less), maintained at 300°C for 1 hour, and then cooled to 25°C to form a polyimide layer having a thickness of 5.0 μm. Thus, a laminate having a polyimide film and a polyimide layer was obtained.

[0414] [Examples 20 and 23]

[0415] The components contained in the resin composition for optical resin layer are the same as those contained in the resin composition for optical resin layer of Example 5, and the compositions of the resin composition for optical resin layer, the first intermediate layer, and the second intermediate layer, and the thicknesses of the optical resin layer, the first intermediate layer, the second intermediate layer, and the resin substrate are changed as shown in Table 1. The laminate was prepared in the same manner as in Example 1. The composition of each resin composition was prepared in such a manner that the content of a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (M403, manufactured by Toagosei Co., Ltd.), dipentaerythritol EO-modified hexaacrylate (A-DPH-6E, manufactured by Shin-Nakamura Chemical Co., Ltd.), and irregular silica fine particles (average particle size 25 nm, manufactured by JGC Catalysts & Chemicals Co., Ltd.), and the content of the polyimide component relative to the solid content other than the solvent became the ratios shown in Table 1.

[0416] [Examples 21 and 22]

[0417] First, the following polyimide resin composition 2 was prepared, and a single-layer polyimide film was manufactured in the same manner as in Example 1. The polyimide resin composition 2 was prepared by adding an acrylic resin (EBECRYL767: manufactured by Daicel) to the polyimide resin composition 1 used in Example 1 so that the content of the acrylic resin was 1.5% by mass relative to the solid content. Next, a laminate was manufactured in the same manner as in Example 1 except that the components contained in the resin composition for the optical resin layer were the same as those contained in the resin composition for the optical resin layer of Example 5, and the compositions of the resin composition for the optical resin layer, the resin composition for the first intermediate layer, and the resin composition for the second intermediate layer, and the thicknesses of the optical resin layer, the first intermediate layer, the second intermediate layer, and the resin substrate were changed as shown in Table 1. The composition of each resin composition was prepared in such a manner that the content of a mixture of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate (M403, manufactured by Toagosei Co., Ltd.), dipentaerythritol EO-modified hexaacrylate (A-DPH-6E, manufactured by Shin-Nakamura Chemical Co., Ltd.) and irregular silica fine particles (average particle size 25 nm, manufactured by JGC Catalysts & Chemicals Co., Ltd.), and the ratio of the content of the polyimide component to the solid content other than the solvent became the ratios shown in Table 1.

[0418] [Comparative Example 4]

[0419] The following resin composition for an optical resin layer was prepared, and a laminate was produced in the same manner as in Example 1 except that the thicknesses of the optical resin layer, the first intermediate layer, the second intermediate layer, and the resin substrate were changed as shown in Table 1.

[0420] The resin composition for an optical resin layer was prepared by adding a UV absorber (DAINSORB P6, manufactured by Yamato Chemicals Co., Ltd.) to the resin composition for an optical resin layer used in Example 1 so that the content of the UV absorber was 8% by mass based on the solid content.

[0421] [Comparative Example 5]

[0422] The following resin composition for an optical resin layer was prepared, and a laminate was produced in the same manner as in Example 17 except that the thicknesses of the optical resin layer, the intermediate layer, and the resin substrate were changed as shown in Table 2.

[0423] The resin composition for an optical resin layer was prepared by adding a UV absorber (DAINSORB P6, manufactured by Yamato Chemicals Co., Ltd.) to the resin composition for an optical resin layer used in Example 1 so that the content of the UV absorber was 8% by mass based on the solid content.

[0424] [evaluate]

[0425] (1) Indentation hardness

[0426] The indentation hardness of each layer was measured using the "Hysitron TI950 TriboIndenter" manufactured by BRUKER. Specifically, first, a block was made by embedding a resin layer cut into 1 mm × 10 mm. Next, an ultrathin slicer ("Ultrathin slicer EMUC7" manufactured by Leica MicroSystems) was used to cut slices with a thickness of 50 nm or more and 100 nm or less without holes and uniform from the block. Then, the remaining block from which the slices were cut was used as a measurement sample. Next, a Berkovich indenter (triangular pyramid, "TI-0039" manufactured by BRUKER) was used to press the indenter vertically into the center of the cross section of the layer of the object of measurement under the following measurement conditions in the cross section obtained by cutting out the above-mentioned slices in the measurement sample. Here, the Berkovich indenter is pressed into the center of the thickness of the layer of the object of measurement at a distance of more than 300 nm from the interface of the layer of the object of measurement and the layer adjacent to the layer of the object of measurement to the central side of the layer of the object of measurement. The case of Example 1 is illustrated. When measuring the indentation hardness of the optical resin layer, the indenter is pressed into a position 1.23 μm away from the interface between the optical resin layer and the first intermediate layer in the thickness direction. In addition, when measuring the indentation hardness of the first intermediate layer, the indenter is pressed into a position 1.3 μm away from the interface between the optical resin layer and the first intermediate layer in the thickness direction and 1.3 μm away from the interface between the first intermediate layer and the second intermediate layer in the thickness direction. In addition, when measuring the indentation hardness of the second intermediate layer, the indenter is pressed into a position 1.25 μm away from the interface between the first intermediate layer and the second intermediate layer in the thickness direction and 1.25 μm away from the interface between the second intermediate layer and the resin substrate in the thickness direction. In addition, when measuring the indentation hardness of the resin substrate, the indenter is pressed into a position 38.7 μm away from the interface between the resin substrate and the second intermediate layer in the thickness direction. Then, after maintaining the residual stress for a certain period of time to relax, unload and measure the maximum load after relaxation. And, use the maximum load P max and contact projection area A p , through P max / A p Calculate the indentation hardness (H IT The contact projection area is the contact projection area obtained by correcting the curvature of the tip of the indenter by the Oliver-Pharr method using a standard sample of fused quartz ("5-0098" manufactured by BRUKER). IT ), 10 locations were measured for each layer, and the arithmetic mean of the measured values ​​for the 10 locations was obtained. It should be noted that when the measured values ​​contained values ​​that deviated from the arithmetic mean by more than ±20%, the measured values ​​were removed and remeasured.

[0427] (Measurement conditions)

[0428] ·Press control method: displacement control method

[0429] Indentation depth: 100nm

[0430] Pressing speed: 10nm / sec

[0431] Loading time: 20 seconds

[0432] Hold time: 5 seconds

[0433] Load unloading speed: 10nm / sec

[0434] Unloading time: 20 seconds

[0435] ·Measurement temperature: 25℃

[0436] (2) Content of the first component constituting the resin substrate

[0437] The ratio of the content of the first component in each layer to the content of the first component in the resin substrate was determined by measuring the cross section of the laminate using the AFM-IR method. The AFM-IR measurement was performed using nanoIR manufactured by Anasys Instruments under the following conditions.

[0438] Light source: tunable pulse laser (1kHz)

[0439] AFM mode: Contact mode (when obtaining AFM-IR spectrum)

[0440] ·Measurement wave number range: 1950cm -1 ~950cm -1

[0441] Wave number resolution: 1.5cm -1

[0442] Coaverages: 512

[0443] Cumulative number of times: 3 times or more

[0444] Polarization angle: 45 degrees

[0445] The IR spectrum of the resin substrate was confirmed, and the peak derived from the C=O stretching vibration was confirmed at 1721cm-1, and the peak derived from the CN stretching vibration was confirmed at 1363cm-1. Since the peaks observed in other polyester resins and polyamide resins could not be confirmed, it was confirmed that the resin substrate was a single polyimide resin. In addition, in the IR spectrum of the resin substrate, the intensity of the peak at 1363cm-1 was set to 1, and the ratio of the intensity of each peak of the first intermediate layer, the second intermediate layer, and the optical resin layer was calculated to calculate the ratio of the content of the first component in each layer. Here, in the IR spectrum, the peak of the C=O stretching vibration derived from the polyimide resin constituting the resin substrate and the peak of the C=O stretching vibration derived from the acrylic resin constituting the first intermediate layer, the second intermediate layer, and the optical resin layer are located in a close position, so the ratio of the intensity of the peak derived from the CN stretching vibration is calculated.

[0446] (3) Adhesion

[0447] First, the laminate was subjected to an accelerated weathering test in accordance with the following JIS K5600-7-8:1999.

[0448] (Conditions that promote weathering test)

[0449] Procedure: Method A involves exposure to water vapor condensation

[0450] UV light: Type 2 UVA (340)

[0451] Irradiation: wavelength 340nm, irradiance 0.63W / m 2 , temperature 23±5℃, black panel temperature 60±3℃, irradiation time 4 hours

[0452] Water vapor condensation: black panel temperature 50±3℃, water condensation time 4 hours

[0453] 1 cycle: The above irradiation and the above water vapor condensation are performed in sequence as 1 cycle

[0454] Number of cycles: 12 cycles

[0455] Next, after the accelerated weathering test, an adhesion test based on the checkerboard tape method was performed according to JIS K5400-8.5.2:1990. First, a cutter was used to cut a checkerboard-like cut at intervals of 1 mm from the optical resin layer side of the laminate to the surface layer of the resin substrate to form 100 grids. Then, a transparent tape (manufactured by NICHIBAN) was pasted on the above grids and then peeled off, and this was repeated 5 times. Then, the state of the grids was observed visually.

[0456] In addition, the results of the adhesion test were evaluated according to the following criteria.

[0457] A: The number of remaining grids in 100 grids is 100.

[0458] B: The number of meshes remaining among 100 meshes is 90 or more and 99 or less.

[0459] C: The number of meshes remaining among 100 meshes is 89 or less.

[0460] (4) Bending resistance

[0461] The following dynamic bending test was performed on the laminate to evaluate the bending resistance. First, a laminate of 20 mm × 100 mm was prepared. Figure 3 As shown in (a), the short side 1C of the laminate 1 and the short side 1D opposite to the short side 1C are fixed to a durability tester (product name "DLDMLH-FS", manufactured by Yuasa System) by using the fixing parts 51 arranged in parallel. Figure 3 As shown in (b), by moving the fixing parts 51 in a manner close to each other, the stacked body 1 is deformed in a folded manner, and, as shown in Figure 3 As shown in (c), after the fixing portion 51 is moved to a position where the interval d between the two opposite short sides 1C and 1D fixed by the fixing portion 51 of the stacked body 1 becomes a predetermined value, the fixing portion 51 is moved in the reverse direction to eliminate the deformation of the stacked body 1. Figure 3 (a)~ Figure 3 As shown in (c), the action of folding the laminate 1 by 180° is repeated 200,000 times by moving the fixing portion 51. At this time, the interval d between the two opposing short sides 1C and 1D of the laminate 1 is 4 mm, 6 mm, 8 mm, and 10 mm. In addition, the laminate is bent in a manner such that the resin substrate is on the outside and the optical resin layer is on the inside. The results of the dynamic bending test are evaluated according to the following criteria.

[0462] A: When the interval d was 4 mm, 6 mm, 8 mm, and 10 mm, the laminated body did not suffer from cracking, breaking, or peeling.

[0463] B: When the interval d is 6 mm, 8 mm, or 10 mm, the laminate does not suffer from cracks, breaks, or peeling.

[0464] C: When the interval d is 8 mm or 10 mm, the laminate does not suffer from cracks, breaks, or peeling.

[0465] D: When the distance d is 10 mm, the laminate does not suffer from cracks, breaks, or peeling.

[0466] (5) Steel wool resistance

[0467] Using #0000 steel wool ("BON STAR" manufactured by Nippon Steel Wool Co., Ltd.), a 1 kg / cm2 pressure was applied to the surface of the optical resin layer side of the laminate of the example. 2 The laminate was rubbed back and forth 3500 times at a speed of 50 mm / sec with a load of 1.50 mm / sec. Then, the surface of the laminate was visually checked for damage and evaluated according to the following criteria.

[0468] A: No damage

[0469] B: There are scars

[0470] (6) Pencil hardness

[0471] The pencil hardness of the surface of the optical resin layer side of the laminate of the embodiment was measured in accordance with JIS K5600-5-4: 1999. At this time, as a pencil hardness tester, a "pencil scratch coating hardness tester (electric type)" manufactured by Toyo Seiki Seisaku-sho Co., Ltd. was used. The measurement conditions were set to an angle of 45°, a load of 1 kg, a speed of 0.5 mm / sec or more and 1 mm / sec or less, and a temperature of 23±2°C.

[0472]

[0473] [Table 2]

[0474]

[0475] [Table 3]

[0476]

[0477] In Examples 1 to 16 and Examples 20 to 23, the first intermediate layer and the second intermediate layer contain the first component constituting the resin substrate, so the adhesion is good after the accelerated weathering test. In addition, in Examples 17 to 19, the intermediate layer contains the first component constituting the resin substrate, so the adhesion is good after the accelerated weathering test. On the other hand, in Comparative Examples 1 to 3, no intermediate layer is configured between the resin substrate and the optical resin layer, so the adhesion is reduced after the accelerated weathering test.

[0478] In Examples 1 to 19, Examples 1 to 7, Examples 9 to 12, and Examples 14 to 19, the ratio of the content of the first component in each layer to the content of the first component in the resin substrate has a predetermined relationship, so the bending resistance is also good.

[0479] In addition, in Examples 1 to 5, Examples 9 to 12, and Example 14 among Examples 1 to 19, the ratio of the content of the first component in each layer to the content of the first component in the resin substrate is within the preferred range, thereby promoting excellent adhesion after the weathering test, and also good bending resistance and hardness characteristics.

[0480] Tables 1 to 3 show that, although the higher the indentation hardness of the optical resin layer, the better the hardness property, the smaller the difference between the indentation hardness of the optical resin layer and the indentation hardness of other layers is, the better the bending resistance is.

[0481] In addition, it is taught that when the indentation hardness of the optical resin layer and the indentation hardness of the resin substrate are both high, and the indentation hardness of the first intermediate layer and the indentation hardness of the second intermediate layer are slightly lower than the indentation hardness of the optical resin layer and the indentation hardness of the resin substrate, the bending resistance becomes good. Specifically, it is taught that when the difference Δ1 between the indentation hardness of the first intermediate layer and the indentation hardness of the optical resin layer, and the difference Δ2 between the indentation hardness of the first intermediate layer and the indentation hardness of the resin substrate are both small, preferably less than 120MPa, the bending resistance becomes good. Similarly, it is taught that when the difference between the indentation hardness of the second intermediate layer and the indentation hardness of the optical resin layer, and the difference between the indentation hardness of the second intermediate layer and the indentation hardness of the resin substrate are both small, the bending resistance becomes good. More specifically, it is taught that when the difference Δ1 between the indentation hardness of the first intermediate layer and the indentation hardness of the optical resin layer, and the difference Δ2 between the indentation hardness of the first intermediate layer and the indentation hardness of the resin substrate are small, preferably less than 30MPa, the bending resistance becomes good. Similarly, it is taught that when the difference between the indentation hardness of the second intermediate layer and the indentation hardness of the optical resin layer and the difference between the indentation hardness of the second intermediate layer and the indentation hardness of the resin substrate is small, the bending resistance becomes good. It is believed that the reason is that the tensile stress and compressive stress applied when the laminate is bent are well dispersed.

[0482] In particular, in the above case, when the difference Δ2 between the indentation hardness of the first intermediate layer and the indentation hardness of the resin substrate is smaller than the difference Δ1 between the indentation hardness of the first intermediate layer and the indentation hardness of the optical resin layer, the first intermediate layer has better followability to the resin substrate, and thus has good bending resistance. That is, it is taught that the adhesion, hardness characteristics, and bending resistance are all good.

[0483] Similarly, it is taught that when the indentation hardness of the optical resin layer and the indentation hardness of the resin substrate are both high and the indentation hardness of the intermediate layer is slightly lower than the indentation hardness of the optical resin layer and the indentation hardness of the resin substrate, the bending resistance becomes good. Specifically, it is taught that when the difference Δ3 between the indentation hardness of the intermediate layer and the indentation hardness of the optical resin layer and the difference Δ2 between the indentation hardness of the intermediate layer and the indentation hardness of the resin substrate are both small, preferably less than 120 MPa, the bending resistance becomes good. More specifically, it is taught that when the difference Δ3 between the indentation hardness of the intermediate layer and the indentation hardness of the optical resin layer and the difference Δ4 between the indentation hardness of the intermediate layer and the indentation hardness of the resin substrate are small, preferably less than 30 MPa, the bending resistance becomes good. It is believed that the reason for this is that

[0484] As described above, the tensile stress and compressive stress applied when the laminate is bent are well dispersed.

[0485] In particular, in the above case, when the difference Δ4 between the indentation hardness of the intermediate layer and the indentation hardness of the resin substrate is smaller than the difference Δ3 between the indentation hardness of the intermediate layer and the indentation hardness of the optical resin layer, the intermediate layer has good followability to the resin substrate, and thus good bending resistance. That is, it is taught that the adhesion, hardness characteristics, and bending resistance are all good.

[0486] On the other hand, it is believed that when the indentation hardness of the first intermediate layer and the second intermediate layer is significantly lower than the indentation hardness of the optical resin layer and the indentation hardness of the resin substrate, and when the indentation hardness of the intermediate layer is significantly lower than the indentation hardness of the optical resin layer and the indentation hardness of the resin substrate, stress is locally concentrated when the laminate is bent, thereby reducing the bending resistance.

[0487] The present disclosure provides the following [1] to

[19] .

[0488] [1] A laminate comprising an optical resin layer, a first intermediate layer, a second intermediate layer, and a resin substrate in this order,

[0489] The first intermediate layer and the second intermediate layer each contain a first component constituting the resin base material.

[0490] [2] A laminate as described in [1], wherein the ratio of the content of the first component in each of the layers to the content of the first component in the resin substrate increases in the order of the optical resin layer, the first intermediate layer, the second intermediate layer and the resin substrate.

[0491] [3] The laminate according to [2], wherein, when the content of the first component in the resin substrate is 100%,

[0492] The ratio of the content of the first component in the second intermediate layer to the content of the first component in the resin substrate is 50% or more and 95% or less,

[0493] The ratio of the content of the first component in the first intermediate layer to the content of the first component in the resin substrate is 10% or more and 50% or less,

[0494] A ratio of a content of the first component in the optical resin layer to a content of the first component in the resin substrate is 0% or more and 10% or less.

[0495] [4] The laminate according to any one of [1] to [3], wherein the first intermediate layer and the second intermediate layer each contain a second component constituting the optical resin layer.

[0496] [5] The laminate according to any one of [1] to [4], wherein the indentation hardness of the optical resin layer is greater than the indentation hardness of the first intermediate layer and the indentation hardness of the second intermediate layer, respectively.

[0497] The indentation hardness of the resin substrate is greater than the indentation hardness of the first intermediate layer and the indentation hardness of the second intermediate layer.

[0498] [6] The laminate according to [5], wherein the indentation hardness of the optical resin layer is 400 MPa or more,

[0499] The indentation hardness of the first intermediate layer and the indentation hardness of the second intermediate layer are respectively 100 MPa or more and 400 MPa or less.

[0500] The resin substrate has an indentation hardness of 240 MPa or more and 600 MPa or less.

[0501] [7] The laminate according to any one of [1] to [6], wherein the thickness of the first intermediate layer and the thickness of the second intermediate layer are respectively 1 μm or more and 5 μm or less.

[0502] [8] A laminate comprising an optical resin layer, an intermediate layer and a resin substrate in this order,

[0503] The intermediate layer contains a first component constituting the resin substrate and a second component constituting the optical resin layer.

[0504] [9] A laminate comprising an optical resin layer, an intermediate layer and a resin substrate in this order,

[0505] The intermediate layer contains the first component constituting the resin substrate.

[0506] When the laminate was subjected to an accelerated weathering test in accordance with JIS K5600-7-8:1999 described below and then subjected to an adhesion test by a cross-cut tape method in accordance with JIS K5400-8.5.2, the number of remaining grids was 90 or more out of 100 grids.

[0507] (Conditions that promote weathering test)

[0508] Procedure: Method A involves exposure to water vapor condensation

[0509] UV light: Type 2 UVA (340)

[0510] Irradiation: irradiance 0.63W / m 2 , temperature 23±5℃, black panel temperature 60±3℃, irradiation time 4 hours

[0511] Water vapor condensation: black panel temperature 50±3℃, water condensation time 4 hours

[0512] 1 cycle: The above irradiation and the above water vapor condensation are performed in sequence as 1 cycle

[0513] Number of cycles: 12 cycles

[0514]

[10] The laminate according to [9], wherein the intermediate layer contains a second component constituting the optical resin layer.

[0515]

[11] A laminate as described in any one of [8] to

[10] , wherein the ratio of the content of the first component in each of the layers to the content of the first component in the resin substrate increases in the order of the optical resin layer, the intermediate layer and the resin substrate.

[0516]

[12] The laminate according to

[11] , wherein, when the content of the first component in the resin substrate is 100%,

[0517] The ratio of the content of the first component in the intermediate layer to the content of the first component in the resin substrate is 10% or more and 95% or less,

[0518] A ratio of a content of the first component in the optical resin layer to a content of the first component in the resin substrate is 0% or more and 10% or less.

[0519]

[13] The laminate according to any one of [8] to

[12] , wherein the indentation hardness of the optical resin layer is greater than the indentation hardness of the intermediate layer,

[0520] The indentation hardness of the resin substrate is greater than the indentation hardness of the intermediate layer.

[0521]

[14] The laminate according to

[13] , wherein the indentation hardness of the optical resin layer is 400 MPa or more,

[0522] The indentation hardness of the intermediate layer is 100 MPa or more and 400 MPa or less.

[0523] The resin substrate has an indentation hardness of 240 MPa or more and 600 MPa or less.

[0524]

[15] The laminate according to any one of [8] to

[14] , wherein the thickness of the intermediate layer is 1 μm or more and 5 μm or less.

[0525]

[16] The laminate according to any one of [1] to

[15] , wherein the resin substrate contains a resin component having at least one selected from the group consisting of an imide skeleton, an amide skeleton, and an ester skeleton.

[0526]

[17] The laminate according to any one of [1] to

[16] , wherein the thickness of the optical resin layer is 1 μm or more and 20 μm or less.

[0527]

[18] A touch panel member having the laminate according to any one of [1] to

[17] on its surface.

[0528]

[19] A display device comprising: a display panel; and

[0529] The laminated body according to any one of [1] to

[17] , arranged on the viewer side of the display panel.

[0530] Description of Reference Numerals

[0531] 1, 1A, 1B ... laminate

[0532] 2…Resin base material

[0533] 3…1st middle layer

[0534] 4…2nd intermediate layer

[0535] 5…Resin base material

[0536] 6…Middle Layer

[0537] 10…Display device

[0538] 11…Display Panel

Claims

1. A laminate comprising an optical resin layer, a first intermediate layer, a second intermediate layer and a resin substrate in this order, The first intermediate layer and the second intermediate layer each contain a first component constituting the resin base material.

2. The laminate according to claim 1, wherein The ratio of the content of the first component in each of the layers to the content of the first component in the resin substrate increases in the order of the optical resin layer, the first intermediate layer, the second intermediate layer, and the resin substrate.

3. The laminate according to claim 2, wherein: When the content of the first component in the resin substrate is 100%, The ratio of the content of the first component in the second intermediate layer to the content of the first component in the resin substrate is 50% or more and 95% or less, The ratio of the content of the first component in the first intermediate layer to the content of the first component in the resin substrate is 10% or more and 50% or less, A ratio of a content of the first component in the optical resin layer to a content of the first component in the resin substrate is 0% or more and 10% or less.

4. The laminate according to any one of claims 1 to 3, wherein The first intermediate layer and the second intermediate layer each contain a second component constituting the optical resin layer.

5. The laminate according to any one of claims 1 to 3, wherein The indentation hardness of the optical resin layer is greater than the indentation hardness of the first intermediate layer and the indentation hardness of the second intermediate layer, respectively. The indentation hardness of the resin substrate is greater than the indentation hardness of the first intermediate layer and the indentation hardness of the second intermediate layer.

6. The laminate according to claim 5, wherein: The indentation hardness of the optical resin layer is above 400 MPa. The indentation hardness of the first intermediate layer and the indentation hardness of the second intermediate layer are respectively 100 MPa or more and 400 MPa or less. The resin substrate has an indentation hardness of 240 MPa or more and 600 MPa or less.

7. The laminate according to any one of claims 1 to 3, wherein The thickness of the first intermediate layer and the thickness of the second intermediate layer are respectively 1 μm or more and 5 μm or less.

8. A laminate comprising an optical resin layer, an intermediate layer and a resin substrate in this order, The intermediate layer contains a first component constituting the resin base material and a second component constituting the optical resin layer.

9. A laminate comprising an optical resin layer, an intermediate layer and a resin substrate in this order, The intermediate layer contains a first component constituting the resin substrate, After the laminate is subjected to an accelerated weathering test based on JIS K5600-7-8:1999 described below, when an adhesion test is performed by a cross-cut tape method based on JIS K5400-8.5.2, the number of remaining grids out of 100 grids is 90 or more, Conditions that promote weathering testing Procedure: Method A involves exposure to water vapor condensation UV light: Type 2 UVA (340) Irradiation: irradiance 0.63W / m 2 , temperature 23±5℃, black panel temperature 60±3℃, irradiation time 4 hours Water vapor condensation: black panel temperature 50±3℃, water condensation time 4 hours 1 cycle: The irradiation and the water vapor condensation are performed sequentially as 1 cycle Number of cycles: 12 cycles.

10. The laminate according to claim 9, wherein The intermediate layer contains a second component constituting the optical resin layer.

11. The laminate according to claim 8 or claim 9, wherein: The ratio of the content of the first component in each of the layers to the content of the first component in the resin substrate increases in the order of the optical resin layer, the intermediate layer, and the resin substrate.

12. The laminate according to claim 11, wherein When the content of the first component in the resin substrate is 100%, The ratio of the content of the first component in the intermediate layer to the content of the first component in the resin substrate is 10% or more and 95% or less, A ratio of a content of the first component in the optical resin layer to a content of the first component in the resin substrate is 0% or more and 10% or less.

13. The laminate according to claim 8 or claim 9, wherein: The indentation hardness of the optical resin layer is greater than the indentation hardness of the intermediate layer, The indentation hardness of the resin substrate is greater than the indentation hardness of the intermediate layer.

14. The laminate according to claim 13, wherein The indentation hardness of the optical resin layer is above 400 MPa. The indentation hardness of the intermediate layer is 100 MPa or more and 400 MPa or less. The resin substrate has an indentation hardness of 240 MPa or more and 600 MPa or less.

15. The laminate according to claim 8 or claim 9, wherein: The intermediate layer has a thickness of 1 μm or more and 5 μm or less.

16. The laminate according to claim 1, claim 2, claim 8 or claim 9, wherein: The resin substrate contains a resin component having at least one selected from the group consisting of an imide skeleton, an amide skeleton, and an ester skeleton.

17. The laminate according to claim 1, claim 2, claim 8 or claim 9, wherein: The optical resin layer has a thickness of 1 μm or more and 20 μm or less. 18 . A touch panel member comprising the laminate according to claim 1 , claim 2 , claim 8 or claim 9 on its surface.

19. A display device comprising: a display panel; and The laminated body according to claim 1, claim 2, claim 8 or claim 9, arranged on the viewer side of the display panel.

Citation Information

Patent Citations

  • Preparation of iron powder carrier for developer

    JP1988058358A

  • Polyamide-imide precursor, polyamide-imide film, and display element including the same

    JP2018506611A

  • Polyimide film, method for producing polyimide film, laminate, display surface material, touch panel member, liquid crystal display device, and organic electroluminescent display

    JP2019073013A

  • Laminate, surface material for display, touch panel member, liquid crystal display device, and organic electroluminescence display device

    JP2020203479A

  • Optical film and image display device

    WO2018070523A1